Vertical multi-branch radial boreholes for guided hydraulic fracture propagation and cavity connection - Yaoyao Sun; Minghao Wang; Xiaoguang Wu; Gensheng Li; Zhongwei Huang; Zixiao Xie; Wenchao Zou; Tengda Long; Bo Zhang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Prokaryotic Argonautes as programmable tools for foodborne biological hazards detection: mechanisms, applications, and prospects - Jing-bo Jiao; Cheng-long Zhao; Jiang-li Cao; Tong Lin; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Critical Reviews in Food Science and Nutrition, 2026)

Titanium-in-quartz thermometry constraints on the multi-stage metamorphic evolution and tectonic implications of pelitic UHT granulites in the Helanshan Complex, North China Craton - Ze-Song Wang; Zhi-Bo Tian; Long-Long Gou; Xiao-Fei Xu; Chao Zhang; Yue Liu (Precambrian Research, 2026)

Model simulation of M2 tide-induced turbulent mixing in the deepest trench on Earth - Hongzhou Xu; Liu Yu; Shiqiu Peng; Bo Hong; Qi’an Chen; Huichang Jiang; Philip Adam Vetter; Zheyang Zhang; Tong Long; Ying Lu (Ocean Modelling, 2026)

An improved grout bag–secondary grouting (GBSG) method with time-dependent viscosity modeling for hydrodynamic sealing in karst groundwater conduits - Miao Piao; Qiao Wang; Fusheng Zha; Dongmei Zhang; Long Xu; Bo Kang; Shixian Ren (Journal of Hydrology, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Microplastics exacerbate the toxicity of perfluorooctanoic acid to human cells via cell membrane damage and internalization increases - Qianwen Jiang; Gonghao Liu; Zihang Zeng; Xiaofeng Liu; Fengzhou Xu; Weichao Wang; Caicheng Long; Peng Zhang; Bo Feng; Taiping Qing (Journal of Environmental Chemical Engineering, 2026)

Constructing Cu0-Cu+ sites inside carbon matrix for Fenton-like degradation of oxytetracycline and reduction of aromatic nitro compounds - Ye-Xia Li; Duo-Wei Ma; Bo Liu; Wen-Long Duan; Tian-Fang Cui; Lei Zhang; Jian Luan (Journal of Environmental Chemical Engineering, 2026)

Medium-pressure metamorphism and low-pressure metamorphic overprinting of the Qinling Complex in the Taibai area of the Qinling Orogenic Belt, China and their tectonic implications - Zhi-Bo Tian; Long-Long Gou; Feng Zhou; Ye-Ting Ma; Yue Liu; Ze-Song Wang (Journal of Asian Earth Sciences, 2026)

The role of intraspecific trait variation in understory responses to simulated nitrogen deposition - Lingbo Ji; Songbo Tang; Jing Long; Siyu Liu; Nan Liu; Shuguang Jian; Bo Tang; Liping Wei; Hai Ren (Forest Ecology and Management, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Hydrogeochemistry, source apportionment, and Monte Carlo-based health risks of heavy metals in a Carlin-type gold mining area of karst region, Southwest China - Qiguo Hu; Pan Wu; Xuefang Zha; Ke Wang; Ruixue Zhang; Bo Li; En Long (Environmental Pollution, 2026)

Novel temperature-tolerant Schiff base derivative as high-efficiency inhibitor for acid corrosion of N80 steel - Li-Mao Chen; Shuang-Jian Li; Ru-Han Li; Bo-Kai Liao; Xing-Peng Guo; Long-Fei Song (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Triple-phase Interface-induced triboelectric-liquid capacitance coupling: Unlocking high power direct-current triboelectric nanogenerators - Xin-Long Xiao; Jiang-Tao Guo; Sheng-Jie Lin; Wen Yang; Yun-Bo Zhang; Yong Zhang; Pei-Zhi Yang (Chemical Engineering Journal, 2026)

A source-reduction process via mechanical activation assisted K2SO4 roasting and closed-loop recycling of potassium salt for efficient lithium extraction from lepidolite - Dong-qi Song; Shu-hao Dong; Long-long Zhou; Zi-ang Si; Shuai-bo Geng; Huan Li; Hui Guo (Chemical Engineering Journal, 2026)

Inflammation-targeted bioactive SiMo glass-ceramic nanozymes for adaptive and sequential infection-impaired wound repair through precise immunoregulation and antiinfection - Jing Tian; Yanzi Zhao; Yanping Zuo; Xiaochen Su; Long Zhang; Weipeng Qiang; Zuhao Zhang; Minhui Ai; Houjin Zhuang; Qian Huang; Meng Luo; Bo Lei (Chemical Engineering Journal, 2026)

Molecular engineering of a D-A-D-type fluorescent probe for detecting viscosity in environmental and living systems - Jing Shu; Hao-Long Sun; Xu-Bo Fan; Si-Hong Zhou; Gui-Chuan Huang; Ming-Qi Wang (Analytica Chimica Acta, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

Coupling phosphonate oxidation and phosphate sequestration via Cu-La dual sites in La-based layered carbonate hydroxide - Jinbin Lin; Bo He; Yuli Ma; Xue Li; Yan Wei; Baoxue Zhou; Mingce Long (Water Research, 2026)

Structure-process-performance: A systematic framework for deconstructing constructed wetland models - Hai Long Kang; Yin Yang; Sen Yang; Xin Yao; Hui Jiang; Wen-Bo Nie (Water Research, 2026)

BVDV hijacks the IDO1-dependent tryptophan–kynurenine axis to promote viral replication by limiting interferon–STAT1 antiviral signaling - Tian-yi Liu; Shan-shan Liu; Pei-long LI; Yong Zhou; Yu-xin Song; Wei-jia YAO; Ze-chen Zhang; Chong Zhao; Jiao LI; Lan-bo Tian; Nan LI; Yu Liu; et al. (Veterinary Microbiology, 2026)

Driving workload capacity of highway tunnel entrance and exit takeover under non-driving-related tasks: a multi-dimensional information coupling method - Shuangkai Zhu; Bo Liang; Jia An Niu; Rui Su; Haonan Long; Tao Deng; Mengdie Xu (Tunnelling and Underground Space Technology, 2026)

Chlorination-based resource utilization of chromium-bearing metallurgical solid wastes: Ferrochrome-slag evidence, mechanistic analogues, product recovery, and residue safety - Ren-yun Zhang; Sheng-Zhe Jia; Yan Liu; Zhi-yu Fan; Xiao-Qi Liu; Bo Wang; Long Wang; Kun Wang; Ting-an Zhang (Process Safety and Environmental Protection, 2026)

An entomopathogen-based small-RNA delivery system promotes the biocontrol efficacy against termites - Chen-Chen Zhao; Hang Lu; Xiao-Long Mao; Long-Long Sun; Fang-Chan He; Zheng-Xun Lv; Qing-Bo Tang; Cheng-Wei Li; Long Liu (Pesticide Biochemistry and Physiology, 2026)

137Cs and 210Pbex dating to assess sedimentation rates in terraced valley floor fields - Yunqi Zhang; Shucui Liu; Dan Li; Wei Li; Qingfang Tan; Yi Long; Guirong Hou; Ziteng Luo; Haiyan Yi; Yong Wang; Bo Tan (Journal of Hydrology, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Morphological dynamics of complex longitudinal dunes in the Kumtagh Desert: Synergistic effects of tri-directional winds and sediment grain size - Xujiao Han; Eerdun Hasi; Bingqiang Fei; Yunji Zhang; Bingfu Jin; Bo Wu; Long Cheng; Zhizhu Su (Geomorphology, 2026)

Machine learning-optimized coarse-grained simulations reveal multicomponent solvent-regulated phase separation for precise control of porous polymers - Yun Hao Feng; Bo Zhi Chen; Shi Long Zhang; Chu Qi Wang; Yu Ting He; Yuan Gao; Jing-yi Kang; Ling Liang; Qiang Xu; Bin Du; Xin Dong Guo (Chemical Engineering Journal, 2026)

Distribution and migration pattern of lithium in two tonsteins inside the Li-rich coal under groundwater and seawater leaching - Huidi Hao; Bo Jiu; Wenhui Huang; Zhenguang Shang; Zhaoguo Wang; Li Long; Linghao Huang; Yingying Zhao; Haonan Chen (Chemical Geology, 2026)

K2FeO4-modified vinasse biochar reduces chromium accumulation in rice grains and enhances Cr(VI) reduction in paddy soil - Min Xu; Yinchen Da; Yutao Gao; Jun Wu; Chao Chen; Lulu Long; Min Deng; Bo Zhang; Gang Yang; Jing Ma (Environmental Science and Pollution Research, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Dual-functional nanopesticide based on polydopamine-modified metal-organic framework for enhancing the control of Asian Citrus psyllid and inhibiting of Candidatus Liberibacter asiaticus - Wei Hu; Kejing Wang; Qitong Huang; Chaoyun Chen; Zhanjun Lu; Fengxian Yao; Bo Zhu; Zhixiang Zhang; Long Yi; Ning Zhang (Pesticide Biochemistry and Physiology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Dynamic interfacial polarization via electric double layer coupling in semiconductor–liquid–metal junctions for direct-current tribovoltaic nanogenerators - Sheng-Jie Lin; Jiang-Tao Guo; Xin-Long Xiao; Wen Yang; Yun-Bo Zhang; Yong Zhang; Pei-Zhi Yang (Chemical Engineering Journal, 2026)

Lycii Fructus-derived extracellular vesicles-like particles attenuate sodium iodate-induced retinal injury by transporting bioactive cargo molecules - Pan Huang; Xiao-Bo Zhang; Jia-Qi Li; Guan-Wen He; Ying Chen; Ling-Yun Yang; Zai-Long Chi (Chemical Engineering Journal, 2026)

Gravity-assisted dual-mode biosensor based on CbAgo-driven gel-sol transition of DNA hydrogels for Salmonella detection - Jing-bo Jiao; Cheng-long Zhao; Bei-bei Tian; Jiang-li Cao; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Chemical Engineering Journal, 2026)

Atmospheric mechanisms and kinetics of hydroperoxymethyl formate reactions with OH and Criegee intermediates - Sen Yang; Bo Long (Atmospheric Environment, 2026)

Neuroprotection of engineered Clostridium butyricum-pMTL007-GLP-1 in A53T α-synuclein (α-syn) mouse model via PI3K/AKT/GSK-3β - Xin Fang; Yun Wang; Zhenli Long; Bin Liao; Bo Wang; Daojun Hong; Jie Luo; Tingtao Chen (Journal of Zhejiang University-SCIENCE B, 2026)

Landslide susceptibility assessment based on a frequency ratio-ensemble learning framework and InSAR constraints - Feilong Zhao; Bo Hu; Hongjiang Wu; Wen Li; Chenglong Zhang; Long Hei; Li Wang; Wenqing Wu; Li Yang (Advances in Space Research, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Preparation of cactus-aluminum composite coagulant and its study on coagulation in oilfield sewage: Mechanism analysis of oil-water separation and toxicity reduction - Long Dong; Huili Zhang; Hailin Yu; Bo Yu; Chao Liu (Journal of Hazardous Materials, 2026)

Petrogenesis and element enrichment of Miocene leucogranite in the Chongshan Shear Zone, SW China: Constraints from geochronology, geochemistry, and Hf-Sr-Nd isotopes - Liang Huang; Ye Zhou; Zai-Bo Sun; Feng Zhao; Yan Dao; Su-mei Tian; Shu-Cheng Tan; Xue-long Liu; Shi-tao Zhang; Jia-Xi Zhou (Journal of Asian Earth Sciences, 2026)

Spatially explicit estimation of high-resolution irrigation water use across China using earth observation data and deep learning - Yong Bo; Xueke Li; Kai Liu; Shudong Wang; Long Li; Guoxu Li; Hang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Co-exposure to positively charged polystyrene microplastics and butylparaben exacerbates intestinal injury and behavioral abnormalities in zebrafish - Ruixiang Li; Lixiang Chen; Yingjie Tan; Caicheng Long; Peng Zhang; Taiping Qing; Bo Feng (Environmental Pollution, 2026)

Microplastics and phthalate esters in tropical estuaries of Hainan Island, China: Spatial distribution and interrelationship patterns - Bing Cai; Jiashun Shen; Xinrui Long; Ruifeng Liu; Yanyu Zhou; Bo Hu; Jia Xie; Narainrit Chinfak; Hongwei Zhao; Qipei Li (Estuarine, Coastal and Shelf Science, 2026)

Single-nucleus RNA sequencing reveals a spatiotemporal pattern of H2S signaling in Chinese cabbage - Jiao Zhang; Yang Chen; Bo Liu; Yuwei Qin; Yue Luan; He Yin; Wenqi Liu; Limei Chen; Jixian Zhai; Yanxi Pei; Yanping Long; Zhuping Jin (Science China Life Sciences, 2026)

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

Chloride-enhanced degradation of diethyl phthalate in nano- and micro-scale zero valent iron-activated peroxydisulfate system: transformation and regulation of Fe(IV) and free radicals - Senlin Chen; Jie Ji; Fan Zhang; Bo Wang; Long Liu; Jiaolong Qin; Xiaojun Hu (Journal of Environmental Chemical Engineering, 2026)

Sustainable solidification/stabilization of chromium (VI)-contaminated soil using enzyme-carbonated reactive magnesia cement: a novel eco-friendly approach - Min Shi; Dian-Long Wang; Jin-Yu Shi; Wen-Bo Chen; Hai-Long Li; Yue-Suo Yang; Chao-Sheng Tang (Journal of Environmental Management, 2026)

From surface oxidation to systemic toxicity: Co-exposure of UV-aged polyethylene microplastics and carbendazim disrupts rhizosphere soil microbial in strawberry - Lixiang Chen; Caicheng Long; He Hu; Zihang Zeng; Ruixiang Li; Yingjie Tan; Peng Zhang; Taiping Qing; Bo Feng (Journal of Environmental Sciences, 2026)

Spatio-temporal evolution of cross-layer pollution during groundwater recharge in abandoned mines: Experimental study and numerical modeling - Fangying Dong; Tianyuan Zheng; Weijie Zhang; Huiyong Yin; Chenghao Han; Long Li; Bo Zhang; Jiuchuan Wei; Jian Luo (Engineering Geology, 2026)

Synergistic engineering of zincophilic sites and hierarchical porosity in lignin-derived carbon nanofiber networks for ultra-high energy density flexible zinc-ion hybrid capacitors - Lin-Xuan Wu; Bo Wang; Jia-Long Wen; Zhan-hui Yuan; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Elucidating β-ocimene ozonolysis through combined experiments and theoretical calculations: The Criegee intermediate and peroxy radical pathways - Yu Xia; Xiaofeng Tang; Xiaoxiao Lin; Bo Long; Christa Fittschen; Weijun Zhang (Atmospheric Environment, 2026)

Aneuploid gametes produced by triploid Populus ‘Beilinxiongzhu 1#’ transmit higher paternal heterozygosity to progeny - Yaru Sang; Yunyun Xie; Yifan Zhao; Bo Kong; Dawei Cheng; Liang Li; Lexun Ma; Jiahua Du; Meiling Long; Dongliang Cao; Zhang Huajian; Lao Huiqi; et al. (Tree Genetics & Genomes, 2026)

Co-exposure to polystyrene microplastics and perfluorooctanoic acid can exacerbate lipid metabolism disorders and liver damage in adult zebrafish - Sijie Tian; Ruixiang Li; Ya Zeng; Lingfeng Qin; Caicheng Long; Taiping Qing; Peng Zhang; Bo Feng (Journal of Environmental Sciences, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

WTAP-Driven m6A Modification of TIMP1 mRNA Promotes Sepsis-Induced Cardiomyocytes Injury - Ying Tang; Zhaoquan Yi; Bo Huang; Jingxin Wu; Biao Tian; Guoliang Long (Biochemical Genetics, 2026)

Ultra-highly specific and visual detection of Vibrio pathogens in Porphyra using RPA-coupled CRISPR-LbaCas12a-LFD system - Xu-Xu Luo; Hai-Long Huang; Qi-Qin Liu; Hoi-Yan Kwok; Hai-Tao Ma; Hai-Bo Jiang; Rui Yang (Aquaculture, 2026)

Briarane-type diterpenes from a closed-system cultured soft coral Briareum stechei - Lo-Yun Chen; Bo-Rong Peng; Thanh Hao Huynh; You-Ying Chen; Yu-Cheng Chen; Ngoc-Thac Pham; Huong-Giang Le; Quoc-Vu Pham; Phuong Vu Luu; Ying-Mi Lai; Mohamed El-Shazly; Tsong-Long Hwang; et al. (Phytochemistry, 2026)

SMART-assisted discovery of scalaranes from the marine sponge Lendenfeldia sp. and its anti-osteoclastogenesis activity - Quoc-Vu Pham; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Lo-Yun Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai; Tsong-Long Hwang (Phytochemistry, 2026)

Umifenovir protects Procambarus clarkii against white spot syndrome virus by suppressing viral replication and modulating innate immunity - Cheng Chen; Bo-Han Li; Chao-Yu Wang; Er-Long Wang; Tian-Qiang Liu; Zhe Zhao (Fish & Shellfish Immunology, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Mutations in the mucA gene of Pseudomonas aeruginosa promote disease exacerbation - Yi-Han Wang; Jiang-Yu Long; Wen-Bo Xu; Ke-Ming Ning; Si-Yu Meng; Wang-Si-Jiao Shen; Zhao-Ying Liu (Archives of Microbiology, 2026)

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Macro-micro changes of clayey loess subjected to wetting-drying cycles and the effect on mechanical behavior deterioration - Ya-ni Wei; Wen Fan; Hanghang Chen; Bo Yu; Long-sheng Deng; Jia-yu Liang (Soil and Tillage Research, 2026)

Strategy selection for addressing antibiotic pollution in farmland soils based on the analysis of source apportionment and risk decomposition - Bowen Huang; Xingguo Bu; Jing Wang; Long Chen; Bo Su; Qi Zhang; Shenglu Zhou (Journal of Hazardous Materials, 2026)

Ammonolysis and hydrolysis govern multiphase formaldehyde–amine chemistry - Zegang Dong; Bo Long (Journal of Environmental Sciences, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Solidification of high water content marine deposits by a novel in-situ treatment of magnesia-based bio-cement: Insight from clay content effect - Dian-Long Wang; Wen-Bo Chen; Hao-Yu Fang; Zhen-Yu Yin; Xiao-Hua Pan; Chao-Sheng Tang (Engineering Geology, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Research on design and prediction model of tunnel safety micro-deformation radar monitoring system - Zi-heng Gao; Gu-hua Pu; Jin-zhuang Wang; Meng-wei Han; Qiang He; Xiao-long Wang; Jian-bo Yang; Xiao-yu Yin; Jia-gui Duan; Liang Bao; Xi-can Zhao; Wei-jian Liu (Applied Geophysics, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

A hybrid assembly mechanism employs nonreducing polyketide synthase-like logic for partially reduced polyketide formation - Xianyan Zhang; Chuanteng Ma; Ziguang Deng; Xingtao Ren; Kaijin Zhang; Wenxue Wang; Luning Zhou; Yongchun Zhu; Guojian Zhang; Qian Che; Tianjiao Zhu; Hongan Long; et al. (Marine Life Science & Technology, 2026)
Fungal iterative type I polyketide synthases (iPKSs) are commonly classified into nonreducing (NR-), partially reducing (PR-), and highly reducing (HR-) polyketide synthases based on their assembly mechanisms and domain structures. These iPKSs have been considered functionally and evolutionarily distinct, characterized by clear boundaries. However, emerging genomic analyses suggest that the diversity of iPKSs in fungi is far from fully understood. Here, we describe the discovery and characterization of PbPKS1 from a marine-derived fungus Penicillium brocae HDN12-143, which exhibits an atypical domain organization arranged as KR-KS-AT-PT-ACP 1 -ACP 2 -CMeT-TE. Heterologous expression of PbPKS1 resulted in the production of two monohydroxybenzoic acids and two pyrones. In vivo and in vitro characterizations demonstrated that PbPKS1 has the capability to synthesize Cα-methylated partially reducing polyketides, yet involved a NR-PKS-like assembly mechanism, featuring a product template (PT) domain for aldol cyclization and a C-terminal thioesterase (TE) domain for product release. Phylogenetic analysis suggests that PbPKS1 belongs to a non-canonical PR-PKS (nPR-PKS) family, which is a minor grouping across the fungal kingdom, and possibly evolved from an NR-PKS through gene recombination. The discovery of nPR-PKS not only expands the diversity of iPKSs but also provides new insights into the evolutionary development of fungal iPKSs.

Magnetic iron oxide-loaded coal-based activated carbon for Enhanced copper (II) removal: Batch and fluidized bed studies - Wen Fan; Bo Lv; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Fuel, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

The comprehensive comparison of syngas production systems driven by fossil energy and solar energy: Based on dry (CO2) reforming of methane - Ji-Long Yao; Bo-Yu Xu; Shi-Wei Wang; Zhen-Yu Zhang; Ting Li; Wei-Ting Li; Tao Xie (Fuel, 2026)

Tailored plasmonic interfaces on LAS glass-ceramic gratings for high-efficiency electromagnetic wave absorption - Chunyan Ding; Shanshan Fan; Zhengliang Qiu; Zhuoyang Li; Yiteng Zhang; Songsong Wu; Liping Tong; Bo Zhong; Long Xia; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Dynamic evolution of organic aerosols and gaseous compounds from thirdhand smoke - Liu Yang; Wei Zhou; Weiqi Xu; Siqi Zeng; Zijun Zhang; Bo You; Yan Li; Long Jia; Yi Zhang; Xi Chen; Yele Sun (Building and Environment, 2026)

Machine learning-driven parameter calibration for the FDEM model in weathered rock seabed - Bo Han; Chun-lei Zhang; Gen-qiang Peng; Zhi-shuai Zhang; Yun-long Tie; Bo-nan Zhang (Marine Georesources & Geotechnology, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Impact of dietary selenium supplementation on growth performance, rumen fermentation, antioxidant profiles, and meat quality in lambs on a high-concentrate diet - Bibo Li; Xiong Li; Long Cheng; Jiahao Li; Qianqiu Liu; Guoqing Duan; Yining Yan; Yuhang Xu; Junxing Zhao; Bo Wang; Chunxiang Zhang (Animal Feed Science and Technology, 2026)

CD95 ligand drives abdominal aortic aneurysm progression through Caspase-8-mediated GSDMD-dependent endothelial pyroptosis: modulation by SRC kinase - Tian-tian Ke; Chuan Yuan; Yong Yuan; Jin-long Liu; Xue-liang Zhou; Ji-chun Liu; Wan-fen Xiong; Zhi-bo Liu (Apoptosis, 2026)

Research on the migration characteristics of overlying strata and the feasibility of ascending mining in thin coal seam - Bao-ming Fang; Chao Xu; Ying-le Wang; Xiao-feng He; Ding-bo Li; Heng Zhang; Wen Wang; Xiao-long Zhen (Applied Geophysics, 2026)

Molecular identification and characterization of a ‘Candidatus phytoplasma australasiaticum’ -related strain associated with Scaevola taccada virescence disease in China - Hai-Yan Che; Mei-Jiao Hu; Hai-Bo Long; Da-Quan Luo; Shao-Shuai Yu (Physiological and Molecular Plant Pathology, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Nonlinear dynamic modeling and control of marine riser recoil under disturbances and uncertainties - Yuan-Long Yue; Hong-Bo Xu; Shi-Long Sun; Xin Zuo (Ocean Engineering, 2026)

Nonstationary groundwater level responses to coupled human–natural drivers in the Baiyangdian Watershed - Long Zhou; Longcang Shu; Xiaoran Yin; Tianyu Zhou; Yuxi Li; Bo Liu; Chengpeng Lu; Pengnian Yang (Journal of Hydrology, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Nanoliposome strategy for improving bioavailability and anti-acute alcoholic effects of dihydromyricetin through ginsenoside incorporation - Lee-Fong Yau; Meng-Lan Yu; Tian-Tian Tong; Long-Bo Bai; Yu-Hang Zhang; Ya-Ling Yu; Ting Li; Zhi-Hong Jiang (Food Bioscience, 2026)

Efficient fermentation of di-rhamnolipids-rich products by P. aeruginosa using ethanol as solely carbon source - Xingyu Liu; Li Luo; Mengqian Zhao; Deyu Zhang; Bo Chen; Jun Liu; Xuwei Long (Food and Bioproducts Processing, 2026)

A persistent luminescent lateral flow immunoassay for rapid and accurate detection of estradiol in real samples - Chao Huang; Bingni Jia; Runqi Jiang; Qi Li; Xiaofeng Liu; Caicheng Long; Peng Zhang; Bo Feng; Taiping Qing (Analytica Chimica Acta, 2026)

Algal-bacterial consortia-derived cyanophycin reprograms rice seed metabolism for enhanced abiotic stress resilience - Zirui Zhou; Duoduo Chen; Naif Abdullah Al-Dhabi; Caicheng Long; Taiping Qing; Bo Feng; Wangwang Tang; Peng Zhang (Algal Research, 2026)

Flow-Balanced Scheduled Routing and Robust Refueling for Inland LNG-Fuelled Liner Shipping - De-Chang Li; Kun Li; Yu-Hua Duan; Yong-Bo Ji; Zhou-Meng Ai; Fang-Fang Jiao; Hua-Long Yang (Journal of Marine Science and Engineering, 2025)
Inland LNG-fuelled liner shipping is emerging as a significant trend, yet limited refueling infrastructure presents operational challenges. The complexity of inland navigation requires frequent speed adjustments to meet scheduled arrivals, which directly affects fuel consumption and refueling strategies. Additionally, imbalances in domestic and foreign trade container flows further increase operating costs for liner shipping companies. Given estimated weekly demands, considering navigational restrictions such as water depth and bridge clearance, as well as streamflow velocity, port time windows, empty container repositioning, port selection, speed adjustment, and uncertain fuel consumption, two novel models based on empty container arc variables and node variables are formulated, aiming to maximize voyage profit. These models are extended from divisible demand to indivisible demand cases. The explicit expression for the maximum fuel consumption under the worst-case speed deviation is derived, and an external linear approximation algorithm is proposed to linearize the nonlinear models while controlling approximation errors. Furthermore, the NP-hardness of the problem, the strict equivalence of the two modeling approaches, and the solution properties are proved. A case study of LNG-fuelled liner shipping on the Yangtze River shows the following: (1) for divisible demand, both models achieve optimal solutions within seconds, while for indivisible demand, the node-variable model outperforms the arc-variable model; (2) tactical strategies should be flexibly adjusted based on seasonal water depth, fuel prices, carbon taxes, speed deviations, and expected lock passage times; and (3) increasing fuel prices and carbon taxes generally reduce port calls and sailing speeds, suggesting that stricter fuel price and carbon tax policies can support the transition to green shipping. This study provides both theoretical guidance and managerial insights, supporting shipping companies in optimizing operations and promoting the development of sustainable inland shipping.

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

CRISPR/Cas-powered electrochemical sensors for food safety detection: Current state of the art, challenges, and future perspects - Jiali Qiao; Baoqing Bai; Tao Bo; Jinhua Zhang; Ligang Yu; Ying Zhang; Long Ma; Yukun Yang (Trends in Food Science & Technology, 2025)

Effective gauss-newton inversion for 3D magnetotelluric data with arbitrarily anisotropic conductivities - Junjun Zhou; Bo Han; Andreas Junge; Xiangyun Hu; Tiaojie Xiao; Zhidan Long; Ningbo Bai (Physics of the Earth and Planetary Interiors, 2025)

Efficient removal of microplastics through a combined treatment process: Pre-filtration and adsorption - Bo Lv; Wen Fan; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Journal of Environmental Management, 2025)

Ultrasound-assisted supercritical carbon dioxide extraction of lutein from Tropaeolum majus flowers - Xing-Yu Liu; Yin-Long Li; Jing Zuo; Bo Zhu; Hong Ou (Food Chemistry, 2025)

Physics and fiber optic data dual-driven dynamic prediction method for dam foundation settlement - Heming Han; Fusheng Zha; Long Xu; Bo Kang; Xuedong Zhang; Guangqing Wei; Hao Li; Bin Shi (Engineering Geology, 2025)

Optimization of dielectric microwave response of MoS2 through human-machine interaction based on d-d orbital modulation phase engineering - Long Ma; Yunfei He; Sihao Dou; Zhiyuan Dan; Minghao Yang; Long Xia; Dongdong Liu; Bo Zhong; Xiaoxiao Huang (Chemical Engineering Journal, 2025)

Metal stress-modulated extracellular polymeric substances enable enhanced and selective scandium adsorption in Methylobacterium extorquens - Yun Liu; Shujie Shang; Bo Li; Tin Long Cheong; Mengyun Zhang; Han Gao; Edwin Cheung; Yijun Cao (Bioresource Technology, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Synergistic amelioration of glaucoma by exogenous BDNF supplementation and microRNA-93 inhibitors via regulating Rho/ROCK and BDNF/TrkB/CREB signaling pathways - Kaiming Li; Bo Long; Wei Chen; Min Gan; Manhua Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characteristics and distribution patterns of volcanic fractures in the Chaganhua Subsag of the Songliao Basin, China - Ning Li; Xuan-long Shan; Jian Yi; Zhong-bo Li; Kai-fang Cao; Jun Tian; Yun-qian Shi; Qing-lei Leng (Applied Geophysics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Contarinia maculipennis, a worldwide invasive flower and vegetable pest possessing the particularities of rearrangement and tRNA secondary structures of mitogenome: A potential key to revealing its extensive host radiation - Ning-Bo Ma; Xiu-Fang Dong; Yu Ji; Xin Jin; De-Wei Wei; Yan-Fei Li; Zheng-Hao Yue; Wen-Jun Bu; Ke-Long Jiao (Zoologischer Anzeiger, 2025)

Norsesquiterpenoids from terrestrial and marine organisms: Chemistry, activity and possible biosynthetic pathways (1963–2024) - Tao-Tao Xue; Bao-Long Hou; Meng-Meng Yuan; Zhi-Shu Tang; Hong-Bo Xu (Phytochemistry, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Distinct effects of inorganic and organic carbon on nitrate photolysis and micropollutant degradation under Far-UVC (222 nm) irradiation - Qing Bai; Qian-Yuan Wu; Yun-peng Wu; Yu-jia Nong; Zi-Bo Jing; Min-Yong Lee; Wen-Long Wang (Journal of Hazardous Materials, 2025)

A rock-ice avalanche induced complex hazard cascade in the Suku River basin, southeastern Tibetan Plateau - Yuanling Li; Bin Yu; Hai Huang; Jiajia Zhang; You Tian; Bo Gao; Cheng Gong; Long Chen; Dongxu Yang; Qili Xie; Luxu Zhou (Geomorphology, 2025)

3D printed-assisted fabrication of embedded porous solar evaporators for efficient photothermal evaporation - Zhu-Long Yu; Lei Xu; Cai-Hua Liu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Desalination, 2025)

Molecular insights into the adsorption behavior of PFAS on montmorillonite, polyethylene, and polypropylene: A molecular dynamics study - Qiao Wang; Rui Xu; Fusheng Zha; Long Xu; Bo Kang; Heming Han (Computers and Geotechnics, 2025)

Lightweight silicone aerogel-based ceramic composite with integrated non-ablative and ablative characteristics for reusable thermal protection system - Hao Tian; Xiao Dong; Bo Niu; Zhe Su; Aoqing Yan; Xiubing Liang; Yue Xing; Yi Luo; Donghui Long (Chemical Engineering Journal, 2025)

Non-wetting-confined construction of triboelectric surface with crocodile skin-inspired cap-like mechanoreceptors for ultrasensitive tactile sensation - Long-Xiang You; Bo Tang; Qiang-Wu Tan; Xi Chen; Jia-Bin Wei; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Development of biodegradable starch-based lambda-cyhalothrin microcapsules for sustainable long-term pest control and enhanced utilization efficacy - Liang Li; Long Chen; Qian Du; Xiquan Ding; Hongyan Chen; Fei Gao; Bo Cui; Haixin Cui; Zhanghua Zeng (Carbohydrate Polymers, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Enhancement of near-inertial waves by cyclonic eddy in the northwestern South China Sea during spring 2022 - Qi'an Chen; Hongzhou Xu; Dongxiao Wang; Bo Hong; Chunlei Liu; Zheyang Zhang; Huichang Jiang; Wei Song; Tong Long; Ling Wang; Sumin Liu; Rongjie Chen (Ocean Science, 2025)
By analyzing datasets derived from four moorings during spring 2022, this study provides direct evidence that near-inertial waves (NIWs) can be largely enhanced by a passing cyclonic eddy (CE) in the northwestern South China Sea. Results show that the enhancement of NIWs mainly occurred at north side of the CE due to asymmetry of eddy structure. In vertical, the enhancement concentrated at above 200 m and reached peaks at around 100 m. Significant energy transfer rates between the CE and NIWs appeared at the same depth of the enhancement can reach a magnitude of 10−8 m2 s−3 at the CE's edge. Under the impact of the CE, power of the first five NIWs modes was promoted significantly and dominated by the second and third modes. Overall, the CE transferred energy to NIWs before near-inertial kinetic energy reaching its peaks, while NIWs gave energy back to the CE after the peaks.

Terpenoids from Alpinia galanga and their acetylcholinesterase inhibitory activity - Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Shao-Huan Liu; Xiang-Chun Shen; Nen-Ling Zhang (Natural Product Research, 2025)

Will a pre-structure concept be applicable to tunnels in squeezing ground? - Yong Yuan; Bo-Ran Shi; Yun-Lu He; Peng Feng; Jiao-Long Zhang (Tunnelling and Underground Space Technology, 2025)

Higenamine hydrochloride prevents renal inflammation and fibrosis in diabetic nephropathy by inhibiting the STAT3 signaling pathway - Ying Li; Zhi-Hao Ma; Xiao Liu; Wenting Zhu; Long Chen; Wanyi Xu; Lei Wang; Jingquan Dong; Zi-Bo Dong (Toxicology and Applied Pharmacology, 2025)

Anti-inflammatory biscembranoids from aquaculture-derived soft coral Sarcophyton trocheliophorum - Lo-Yun Chen; Bo-Rong Peng; Ngoc Bao An Nguyen; Tsong-Long Hwang; Kuei-Hung Lai; Jui-Hsin Su (Phytochemistry Letters, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic catalytic upcycling of waste plastics with CO2: Mechanisms, innovations, and future perspectives - Zheng Ma; Huan Chen; Zhe Zhang; Bo Niu; Donghui Long; Yayun Zhang (Fuel, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Recent advances in nanomaterial biosensors for the detection of antibiotics to ensure food safety - Bo Long; Qian Zhang; Lintong Zhang; Qiongqiong Xing; Qi Liu; Liying Deng; Fangfang Qu; Rui You; Xuan Wei; Dapeng Ye; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Unveiling the heterogeneity of cellulose separators and lignin-derived electrodes fabricated from different bamboo tissues in supercapacitors application - Si-Meng Chen; Ling-Hua Xu; Chen Zhang; Bo Wang; Jia-Long Wen; Tong-Qi Yuan (Chemical Engineering Journal, 2025)

Pseudomonas bambusae sp.nov., an Aniline Blue-Decolorizing Bacterium Isolated from Decaying Round Bamboo Culms - Xiao-Long He; Jia-Yan Wang; Jin-Jia Liang; Cheng-Jing Ren; Xin-Yi Guo; Wen-Jie Ke; Min Wu; Hong-Zheng Liu; Min Jin; Fang-Li Sun; Shuai-Bo Han (Current Microbiology, 2025)

Satellite-Based Emission Inversion for Air Pollutants and Greenhouse Gases: A Review - Zhe Jiang; Jintai Lin; Tai-Long He; Fei Jiang; Jianbing Jin; Kai Qin; Lu Shen; Panpan Yang; Zengliang Zang; Lin Zhang; Yuzhong Zhang; Bo Zheng; et al. (Journal of Meteorological Research, 2025)

FSRNet: A lightweight remote sensing forest wildfire detection network based on multi-scale, multi-level, and multi-path approaches - Yingping Long; Hongwei Ding; Yuanjing Zhu; Zhijun Yang; Bo Li (Advances in Space Research, 2025)

Long-term simulation of process and hydrogeochemistry of gas field produced water reinjection into a limestone reservoir - Bo Liu; Weifeng Jing; Daixi Long; Jiahong Li; Dan Ding; Kunpeng Cai (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Green spaces and preventable disease and economic burdens in China from 2000 to 2020: A health impact assessment study - Hui-Ling Qiu; Hui-Yun Chen; Yu-Ting Xie; Gang-Long Zhou; Kai-Ze Yang; Hai-Juan Huang; Jian-Cheng Jiang; Xiao-Qi Zhu; Lu Wang; Kexin Yan; Guang-Hui Dong; Shujun Fan; et al. (Landscape and Urban Planning, 2025)

Rnai-mediated knockdown of nuclear receptors impairs cuticle formation by disrupting chitin metabolic pathway in Holotrichia oblita - Zhi-long Niu; Jian Wei; Qian Wang; Yu-bo Yang; Ying-Nan Gao; Lu Li; Jia Jia; Wei Guo; Dan Zhao (Journal of Insect Physiology, 2025)

Functional response and instar preference of Encarsia formosa (Hymenoptera: Aphelinidae) parasitizing Bemisia tabaci (Hemiptera: Aleyrodidae) at different densities and temperatures - Bo Zhang; Guo-Ting Yuan; Peng Han; Krutmuang Patcharin; Perumal Vivekanandhan; Jin-Long Zhang; Jiao Kong; Guo-Hua Chen; Xiao-Ming Zhang (Journal of Asia-Pacific Entomology, 2025)

Experimental investigation on the elastic-plastic failure evolution mechanism of high-temperature hot dry rocks using combined monitoring of acoustic emission and digital image correlation - Qiuyan Wang; Daobing Wang; Xiuhua Li; Yanhong Hou; Mao Sheng; Lieqian Long; Yongliang Wang; Bo Yu (Geothermics, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Selenium-enriched lactic acid bacteria inoculation enhances the quality of Paocai by imparting the microbiome and metabolome - Mingye Peng; Qin Li; Binbin Long; Bo Li; Zhicong Shen; Ning Xu; Yong Hu; Chao Wang; Yang Chen; Mengzhou Zhou (Food Chemistry, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Multifunctional packaging based on gelatin/hydroxyethyl cellulose and green synthetic carbon dots for simultaneous preservation and visual freshness monitoring of pork - Yongshi Chen; Shuaifan Qin; Zhixin Xie; Ming Cao; Long Cheng; Bo Tian; Jiukai Zhang (Food Bioscience, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Revealing the spectral bands that make generic remote estimates of leaf area index in wheat crop over various interference factors and planting conditions - Heli Li; Pingheng Li; Xingang Xu; Haikuan Feng; Bo Xu; Huiling Long; Guijun Yang; Chunjiang Zhao (Computers and Electronics in Agriculture, 2025)

Construction of critical speed threshold model based on psychophysiological perception of driver for road tunnels and analysis of perception mechanism - Can Qin; Bo Liang; Jia’an Niu; Jinghang Xiao; Shuangkai Zhu; Haonan Long; Tao Deng (Tunnelling and Underground Space Technology, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Robustness study of seismic hazard assessment models based on multi-source data - Bo Liu; Haijia Wen; Mingrui Di; Mingyong Liao; Junhao Huang; Long Qian; Yongbo Chu (Gondwana Research, 2025)

Toxic effects of polystyrene microplastics on atrazine in zebrafish: Exogenous toxicity and endogenous mechanism - Zihang Zeng; Lixiang Chen; Ruixiang Li; Yingjie Tan; Xiaofeng Liu; Caicheng Long; Peng Zhang; Taiping Qing; Bo Feng (Environmental Pollution, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Ox-LDL Induces Neuron Apoptosis and Worsens Neurological Outcomes in aSAH via Fas/FADD Pathway - Yabin Song; Chen Yu; Dandan Bo; Junqi Sun; Yong Wang; Pingping Chen; Hanming Wu; Linghong Hong; Zhennan Ye; Long Zhang; Diangui Zhou (Molecular Neurobiology, 2025)

Mooring Evaluation of a Floating Offshore Wind Turbine Platform Under Rogue Wave Conditions Using a Coupled CFD-FEM Model - Bo Li; Hao Qin; Haoran Zhang; Qibin Long; Donghao Ma; Chen Xu (Journal of Marine Science and Engineering, 2025)
As the development of offshore wind energy transforms from coastal to deep-sea regions, designing a cost effective mooring system while ensuring the safety of floating offshore wind turbine (FOWT) remains a critical challenge, especially considering extreme wave environments. This study employs a model coupling computational fluid dynamics (CFD) and finite element method (FEM) to investigate the responses of a parked FOWT platform with its mooring system under rogue wave conditions. Specifically, the mooring dynamics are solved using a local discontinuous Galerkin (LDG) method, which is believed to provide high accuracy. Firstly, rogue wave generation and the coupled CFD-FEM are validated through comparisons with existing experimental and numerical data. Secondly, FOWT platform motions and mooring tensions caused by a rogue wave are obtained through simulations, which are compared with the ones caused by a similar peak-clipped rogue wave. Lastly, analysis of four different mooring design schemes is conducted to evaluate their performance on reducing the mooring tensions. The results indicate that the rogue wave leads to significantly enlarged FOWT platform motions and mooring tensions, while doubling the number of mooring lines with specific line angles provides the most balanced performance considering cost-effectiveness and structural safety under identical rogue wave conditions.

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Research on Operational Risk for Northwest Passage Cruise Ships Using POLARIS - Long Ma; Jiemin Fan; Xiaoguang Mou; Sihan Qian; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
In the context of global warming, polar tourism is developing rapidly, and the demand for polar cruise travel in the Northwest Passage continues to increase, while sea ice has long been a key factor limiting the development of polar cruise tourism. This study focuses on the operational risk of sea ice on cruise ships in the Northwest Passage (NWP), aiming to provide a scientific basis for ensuring the safety of cruise ship navigation and promoting the sustainable development of polar tourism. Based on ice data from 2015 to 2024, this study used the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology recommended by the International Maritime Organization (IMO) to establish three scenarios for the route of ice class IC cruise ships: light ice, normal ice, and heavy ice. The navigable windows were systematically analyzed and critical waters along the route were identified. The results indicate that the navigable windows for IC ice-class cruise ships under light ice conditions are from mid-July to early December, while the navigable period under normal ice conditions is only from mid- to late September, and navigation is not possible under heavy ice conditions. The study identified Larsen Sound, Barrow Strait, Bellot Strait and Eastern Beaufort Sea as critical waters on the NWP cruise route. Among them, Larsen Sound and Eastern Beaufort Sea have a more prominent impact on voyage scheduling because their navigation weeks overlap less with other waters. This study provides a new idea for the risk assessment of polar cruise ships in ice regions. The research results can provide an important reference for the safe operation of polar cruise ships in the NWP and the decision-making of relevant parties.

Model test on dynamic response of coral sand in island dredging airport under wave, tidal and aircraft landing load - Jianxiu Wang; Ansheng Cao; Dongsheng Song; Bo Feng; Hua Zhang; Huboqiang Li; Yanxia Long; Zhenhua Ye (Marine Georesources & Geotechnology, 2025)

Allicin fumigation delays the decline of fruit quality in blueberries via regulation of reactive oxygen species - Siyu Long; Bo Xu; Yating Zhang; Yingchao Qu; Shujuan Ji; Manli Luo; Meilin Li; Bing Bai; Qian Zhou (Postharvest Biology and Technology, 2025)

Bombella intestini: A probiotic honeybee(Apis mellifera)gut bacterium - Meng Jie Jin; Andrew B. Barron; Sheng Yang He; Xu Jiang He; Qiang Huang; Li Zhen Zhang; Zi Long Wang; Xiao Bo Wu; Wei Yu Yan; Zhi Jiang Zeng (Journal of Insect Physiology, 2025)

Superior water disinfection via ozone micro-bubble aeration: Performance and mechanism - Zi-Chen Yang; Lu Peng; Zi-Bo Jing; Wen-Long Wang; Han-Ying Cai; Yi-Qing Jiang; Long-Di Li; Bei Ye; Qian-Yuan Wu (Journal of Hazardous Materials, 2025)

Comparative Research on Vessel Navigability on the Northern Sea Route Based on the NSR Admission Criteria and POLARIS Methodology - Long Ma; Sihan Qian; Xiaoguang Mou; Jiemin Fan; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
At present, sea ice remains a critical factor affecting the safety of vessel operations along the Northern Sea Route (NSR). However, inconsistencies between the navigability outcomes derived from the criteria for the admission of ships in the area of the Northern Sea Route (NSR criteria) and the polar operational limit assessment risk indexing system (POLARIS) methodology present challenges for navigational decision-making. This study aims to conduct a systematic comparison of the POLARIS methodology and the NSR criteria in evaluating the navigability of independently operating vessels classified as Arc4 to Arc9. Through comparative calculations of navigability and the navigability rates for six ice-class vessels across 27 districts using the two methods, this study reveals the consistencies and discrepancies in their navigability outcomes. Firstly, using the POLARIS methodology, the risk index outcome (RIO) is calculated for six ice-class vessels across 27 districts. For these districts, the navigability threshold is defined when 95% or more of the area exhibits an RIO greater than or equal to zero. Secondly, using the NSR criteria, navigability ratios for six ice-class vessels under varying ice conditions are evaluated. A navigability threshold is defined when 95% or more of the ice conditions in a district are classified as navigable. Finally, a quantitative comparison of the weekly navigability ratios obtained by the two methods is conducted to reveal the consistencies and discrepancies in the navigability outcomes of each ice-class vessel across different NSR districts. The results indicate that the consistency between the navigability outcomes of the two methods decreases with lower vessel ice classes, particularly in September and March. In general, the consistency of performance between the two methods in terms of navigability outcomes deteriorates as the vessel ice class decreases and ice conditions become more complex. This study provides a scientific foundation and data-based support for route planning and real-time decision-making in polar waters.

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Analysis of driving factors and suitability assessment for raft aquaculture in the Northern China seas using remote sensing data - Long Gao; Xiao He; Junmin Zhang; Bo Wang; Sijia Tian; Kunfu Wang; Mengnan Chen; Wenzhuo Lin; Xian Wu; Mingrui Fan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Dynamic analysis of a floating offshore wind turbine with ballast water based on a general framework for external-internal flow coupling - Yuanchuan Liu; Bo Liu; Yuhong Long; Fushun Liu (Ocean Engineering, 2025)

Biochar and polyvinyl alcohol (PVA) application improves desert soil pH and water-holding characteristics and enhances Microcoleus vaginatus growth - Gift G. MOYO; Zhiquan HU; Bingtang LI; Long CHENG; Xun WANG; Bo XIAO (Pedosphere, 2025)

Differential magmatism and tectonic evolution during the rift stage within the Baiyun Sag of the Pearl River Mouth Basin in the northern South China Sea - Bo Yan; Xuan-Long Shan; Zhe Wei; Guo-Li Hao; Peng-Lin Zhang; Ling Ma; Zhi-Hao Wang; Pu-Jun Wang; N.G. Boriskina (Gondwana Research, 2025)

A novel type of carbon dots for discriminating yeast cell viability and nuclear labeling - Long Cheng; Zhixin Xie; Ming Cao; Shuaifan Qin; Yongshi Chen; Bo Tian; Zhibiao Feng (Food Bioscience, 2025)

Enhanced electron transfer in FeS2-FeMoO4 heterojunction for nearly 100% singlet oxygen generation in efficient water remediation - Dawei Song; Yukun Pan; Huan Chen; Yaqin Shi; Yanan Huang; Bo Niu; Donghui Long; Yayun Zhang (Chemical Engineering Journal, 2025)

High-attenuation and broadband microwave absorption of robust and thermally stable SiOC ceramic aerogels derived from interpenetrating silicone double network structure - Aoqing Yan; Guixiang Li; Zhe Su; Liang Li; Yi Luo; Hao Tian; Yu Cao; Yayun Zhang; Bo Niu; Donghui Long (Chemical Engineering Journal, 2025)

Light/dark synergy enhances cyanophycin accumulation in algal-bacterial consortia: Boosted strategy for nitrogen recovery from wastewater - Hongyuan Liu; Zirui Zhou; Caicheng Long; Taiping Qing; Bo Feng; Peng Zhang; You-Peng Chen (Bioresource Technology, 2025)

Orius similis prefers to prey on the young larvae of Encarsia formosa parasitizing on Bemisia tabaci - Bo Zhang; Jiao Kong; Jin-Long Zhang; Guo-Ting Yuan; Pei-Wei Xiong; Guo-Hua Chen; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Optimizing the cooling method and parameters for high geothermal tunnel construction by using model experiment - Heng Zhang; Bo Wang; Yiqi Zhao; Zelin Zhou; Xinrong Tan; Long Xiang; Yi Feng (Tunnelling and Underground Space Technology, 2025)

Molecular mechanisms of andrographolide-induced kidney injury and senescence via SIRT3 inhibition - Yi Cai; Liduan Huang; Yanhong Hou; Peiwen Pang; Ying Zhou; Xuan Zhang; Yiyin Long; Huajian Li; Halimulati Muhetaer; Man Zhang; Bo Wu (Toxicology and Applied Pharmacology, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Modeling, analysis and prediction of waste biomass gasification integrated with parallel multi-stack solid oxide fuel cell systems for low CO2 emissions: A mechanistic and data-driven approach - Xiao-long Wu; Keye Li; Yuxiao Yang; Yuan-wu Xu; Jingxuan Peng; Bo Chi; Zhuo Wang; Xi Li (Process Safety and Environmental Protection, 2025)

Reinforcement learning-based backstepping sliding mode heading control for unmanned sailboats - Chen-Ming Li; Bao-Lin Zhang; Yan-Long Cao; Bo Yin (Ocean Engineering, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Yolk@Shell nanoreactors with spatial confinement cobalt species activate peroxymonosulfate for efficient degradation of bisphenol S - Ya Zeng; Lingfeng Qin; Sijie Tian; Caicheng Long; Taiping Qing; Peng Zhang; Bo Feng (Journal of Water Process Engineering, 2025)

Microplastic distribution in large shallow lake sediments: Variations with offshore distance and implications for microbial communities - Long Chen; Yan Li; Bo Su; Bowen Huang; Yifei Qiu; Shenglu Zhou (Journal of Hazardous Materials, 2025)

Modes of occurrence of rare earth elements and yttrium in the subbituminous coal of the Jungar Coalfield, Ordos Basin, North China - Bo Jiu; Zhijun Jin; Huidi Hao; Zhaoguo Wang; Wenhui Huang; Zhenguang Shang; Runchao Liu; Yang Li; Linhao Huang; Binchao Qin; Zixuan Huang; Li Long; et al. (International Journal of Coal Geology, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Oxygen vacancies-enriched CeO2-CoxOy heterostructures facilitate the “trapping-conversion” process of lithium polysulfides for high-performance Li-S batteries - Anran Gao; Qinwen Wu; Hongli Chen; Yukun Pan; Bo Niu; Yayun Zhang; Donghui Long (Chemical Engineering Journal, 2025)

Estimation of SOC using VNIR and MIR hyperspectral data based on spectral-to-image transforming and multi-channel CNN - Aohua Tang; Guijun Yang; Zhenhong Li; Yuchun Pan; Yu Liu; Huiling Long; Weinan Chen; Jing Zhang; Yue Yang; Xiaodong Yang; Bo Xu (Computers and Electronics in Agriculture, 2025)

Interpretable machine learning reveals transport of aged microplastics in porous media: Multiple factors co-effect - Yifei Qiu; Jingyu Niu; Chuchu Zhang; Long Chen; Bo Su; Shenglu Zhou (Water Research, 2025)

3D hierarchical porous hydrogel polymer electrolytes for flexible quasi-solid-state supercapacitors - Haoran Wang; Zhaoxia Hou; Yue Wang; Haibo Long; Depeng Zhang; Zhongchao Fu; Nan Wu; Zihui Zhai; Bo Wang (Chemical Engineering Journal, 2025)

Nitrogenous chemical constituents and their antitumor activities evaluation in vitro from the aerial parts of Corydalis impatiens (pall.) Fisch - Ze-dong Nan; Yi-dong Zhu; Chao-fan Deng; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Natural Product Research, 2025)

Driving risk assessment in exit areas of highway tunnels based on driving behavior characteristics: Methods and case studies - Bo Liang; Shuangkai Zhu; Haonan Long; Jia An Niu; Can Qin; Haoming Li (Tunnelling and Underground Space Technology, 2025)

Adrenomedullin gene delivery rescues estrogen production in Leydig cells via the inhibition of TGF-β1/Smads signaling pathway - You-wen Luo; Xia-lian Zhu; Zhi-min Yang; Jian-hua Zhou; Tong Tao; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2025)

An improved groundwater vulnerability evaluation model based on random forest algorithm and spatio-temporal change prediction method - Bo Li; Pan Wu; Menghua Li; Lixia Chen; Lei Yang; Jie Long (Process Safety and Environmental Protection, 2025)

Microbial extracellular electron transfer: A promising strategy for heavy metal removal mechanisms, regulation and future development - Hui Xi; Bo Liu; Xilin Li; Xizi Long; Yingying Sun; Wendong Wang; Hui Wang (Journal of Water Process Engineering, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

The Early Jurassic sedimentary records in the Central Lhasa Terrane, southern Tibet: Implications for the subduction and accretion of the Tethys Ocean - Bo Li; Wen-Guang Yang; Zhen Yang; Li-Dong Zhu; Nan Li; Yao Zhong; Long Xie; Yuan-Jun Mai (Journal of Asian Earth Sciences, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Cross-modal semantic transfer for point cloud semantic segmentation - Zhen Cao; Xiaoxin Mi; Bo Qiu; Zhipeng Cao; Chen Long; Xinrui Yan; Chao Zheng; Zhen Dong; Bisheng Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Reduction in sediment yields from karst terrain in SW China over the past 600+ years - Yunqi Zhang; Bangrun Guo; Wei Li; Lan Tang; Xinxin Zhang; Yi Long; Xinbao Zhang; Bo Tan; Ziteng Luo; Xun Hu; Yong Wang (Global and Planetary Change, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Oxidation mechanism of methane fuel blended with dimethyl ether/hydrogen/ammonia via ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2025)

Relationship between the molecular structure of soluble organic matter in a subbituminous coal and the electrochemical properties of prepared supercapacitor - Hao Xu; Yu-Qian Zhang; Xue-Liang Yao; Chen Wang; Qi Zhang; Bo Long; Chen-Chen Guo; Xing Fan (Fuel, 2025)

Activity detection of lactic acid bacteria based on fluorescence color difference of boron and nitrogen co-doped carbon dots - Zhixin Xie; Ming Cao; Yongshi Chen; Long Cheng; Shuaifan Qin; Bo Tian; Zhanmei Jiang (Food Bioscience, 2025)

Microplastics release from infant feeding bottles and milk storage bags - Long Zhao; Yiying Gu; Hua Cai; Xin Xu; Jianguo Yu; Jing Li; Ying Shen; Leiyan Zhu; Yan Jin; Mei Zhang; Ruihua Dong; Bo Chen (Food Control, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Refined Inversion Analysis of 3D Ground Stress Field Based on Random Field - Meng-bo Wang; Du-min Kuang; Long Chen; Zhao-bo Song; Cheng Peng (Geotechnical and Geological Engineering, 2025)

Comprehensive Risk Assessment of Heavy Metals Based on Pollution Sources: A Case Study for Agricultural Soils from Southwest China - Yunxia Zhang; Long Li; Bo Song; Renzhi Xu; Ziyang Zhou; Liangliang Zhu; Lang Zhou (Exposure and Health, 2025)

Simultaneous Quantification of Total Antibody and Conjugated Payload for DS001 in Rat Serum Using a Hybrid Immuno-Capture LC–MS/MS - Xiong Yu; Weiqiang Li; Wensi Huang; Bo Xiao; Jing Long; Qi Wang; Guifeng Wang; Chunhe Wang; Mingming Yu; Jinghua Yu; Xingxing Diao (The AAPS Journal, 2025)

Winter-spring droughts exacerbated PM2.5-O3 compound pollution? Evidence from China - Bo Wu; Feng Jiang; Keliang Long; Jiao Zhang; Chunqiong Liu; Kai Shi (Science of The Total Environment, 2025)

Spectral properties regulation for the performance improvement of solar-driven methane dry reforming reactor based on the photothermal synergistic catalysis - Ji-Long Yao; Zhen-Yu Zhang; Bo-Yu Xu; Ting Li; Tao Xie (Fuel, 2025)

Parametric study on the methanol/diesel JCCI mode with dual-direct injection system in a light-duty engine - Bo Li; Wei Tan; Yunpeng Wei; Liyun Fan; Yang Wang; Xianyin Leng; Ge Xiao; Wuqiang Long (Fuel, 2025)

Enhanced protection and bioavailability of Lycium barbarum leaf extract through encapsulation in whey protein isolate and bovine serum albumin nanoparticles - Zhi-Jing Ni; Chun-Bo Liu; Ying Xue; Hao Huang; Yi-Long Ma; Kiran Thakur; Ya-Fang Shang; Mohammad Rizwan Khan; Zhao-Jun Wei (Food Chemistry, 2025)

Coumarins rather than alkylamides evoke the numbing orosensation of pomelo peel - Guijie Li; Xuting Wang; Qundi Wang; Leng Han; Junying Bai; Fusheng Wang; Bo Yu; Zhaojun Liu; Xingyao Long; Yujiao Cheng (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

Flexural performance and crack width prediction of steel-UHTCC composite bridge decks with wet joints - Jing-Zhong Tong; Yun-Long Chen; Qing-Hua Li; Jian-Bo Dai; Guo-Zhong Wang; Jia-Jia Shen; Wei Gao; Shi-Lang Xu (Engineering Structures, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

High-Performance wave loss capability by Constructing Well-Defined hierarchical aerogel framework with strongly coupled Carbon/CeO2 interface - Yun-Xia Bai; Da-Peng Liu; Lu Zhou; Bo Cai; Pei-Yan Zhao; Hua-Long Peng; Yu Zhang; Qi-Fan Xuan; Wen-Hao Liang; Zhi-Ling Hou; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

Life-cycle and economic assessments of DHA-biogas hierarchical production system utilizing microalgae biomass and residues - Yilin Xu; Chaoyang Wei; Bo Li; Wenbo Li; Jing Han; Yan Nie; Zhuo Li; Long Xu (Chemical Engineering Journal, 2025)

A new approach to high conversion CO2 hydrate sequestration by CO2/water emulsion injection into marine sediments - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Liang-Liang Ren; Ming Wang; Dan Rao; Yong-Quan Liu; Yi-Bo Hao; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Reaction between peracetic acid and carbonyl oxide: Quantitative kinetics and insight into implications in the atmosphere - Chao-Lu Xie; Hao Yang; Bo Long (Atmospheric Environment, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Recycling waste tiles and waste catalysts for high-strength eco-porous ceramics in building applications - Ya-Wen Lin; Wei-Ting Lin; Bo-Xuan Zhang; Kae-Long Lin (Sustainable Chemistry and Pharmacy, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Nitrogen dynamic transport processes shaped by watershed hydrological functional connectivity - Ming Lei; Yu Long; Taoxi Li; Yichun Ma; Guangjie Zhang; Bo Peng; Zhongwu Li; Yaojun Liu (Journal of Hydrology, 2024)

N-coordinated iron sites dispersed in porous carbon frameworks to activate peroxymonosulfate for efficient sulfisoxazole degradation and real hospital wastewater decontamination - Chunxiu Yu; Lingyun Gu; Zelin Wu; Kexin Chen; Yi Wu; Li Zhang; Quan Long; Hongle Shi; Zhaokun Xiong; Bo Lai (Journal of Hazardous Materials, 2024)

An experimental study on monitoring and early warning of spontaneous coal combustion fires using CPM - Liyang Gao; Bo Tan; Long Fan; David Cliff; Jiliang Huang; Haiyan Wang; Biao Kong (Journal of Environmental Chemical Engineering, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Microplastic pollution in Taihu Lake: Spatial distribution from the lake inlet to the lake centre and vertical stratification in the water column - Long Chen; Shenglu Zhou; Bo Su; Yifei Qiu; Yan Li (Environmental Pollution, 2024)

Exposure to greenspaces sourced soils improves mice gut microbiota - Gang-Long Zhou; Yan Xie; Yi-Dan Zhang; Lu Wang; Yu-Ting Xie; Hui-Ling Qiu; Xiao-Qi Zhu; Jian-Cheng Jiang; Yan Yang; Mingdeng Xiang; Guang-Hui Dong; Yuanzhong Zhou; et al. (Environmental Pollution, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Concentric Compressive Behavior and Design of Stainless Steel–Concrete Double-Skin Composite Tubes Influenced by Dual Hydraulic Pressures - Jian-Tao Wang; Yang Yang; Kai-Lin Yang; Deng-Long Hu; Long-Bo Xu; Jun-Xin Li (Journal of Marine Science and Engineering, 2024)
The external hydraulic pressure and internal medium pressure acting on submarine pipelines can lead to the coupling effect of active and passive constraints on the mechanical performance of steel–concrete double-skin composite tubes, resulting in a significantly different bearing capacity mechanism compared to terrestrial engineering. In this paper, the full-range concentric compressive mechanism of new-type stainless steel–concrete double-skin (SSCDS) composite tubes subjected to dual hydraulic pressure was analyzed by the finite element method. The influence of geometric–physical parameters at various water depths was discussed. The key results reveal that imposing dual hydraulic pressures significantly improves the confinement of double-skin tubes to encased concrete, resulting in a higher axial compressive strength and a non-uniform stress distribution; increasing the material strengths of concrete, outer tubes and inner tubes results in an approximately linear enhancement in axial bearing capacity; enhancing the diameter-to-thickness ratios of outer tubes and inner tubes can decrease the bearing capacity of SSCDS composite tubes; and the axial compression strength of SSCDS composite tubes with a higher hollow ratio of 0.849 tends to decrease with increasing outer hydraulic pressure. A practical method that integrates the effects of dual hydraulic pressures was developed and validated for the strength calculation of SSCDS composite tubes. This research provides fundamental guidelines for the application of pipe-in-pipe structures in deep-sea engineering.

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Quercetin intervention mitigates small intestinal damage and immunologic derangement induced by polystyrene nanoplastics: Insights from multi-omics analysis in mice - Long Zhao; Jianheng Zheng; Yiying Gu; Xin Xu; Jianguo Yu; Jing Li; Shuyu Yang; Bo Chen; Jun Du; Ruihua Dong (Environmental Pollution, 2024)

Chitin nanocrystal Pickering emulsions for sustainable release pesticide microencapsulation with superior leaf adhesion and enhanced safety - Long Chen; Liang Li; Hongyan Chen; Bo Cui; Fei Gao; Jinming Gao; Xiang Zhao; Yan Wang; Haixin Cui; Zhanghua Zeng (Chemical Engineering Journal, 2024)

High anisotropy 2D large-size iron-based coral for C-band ultra-wide microwave absorption - Chunyan Ding; Chengshuai Shao; Zhuoyang Li; Xiaozhen Ren; Songsong Wu; Qianqian Zhang; Chuncheng Wei; Long Xia; Bo Zhong; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2024)

Bioenergetic-active photoluminescent bioactive Nanodressing for proangiogenic MRSA infected wound repair and microenviroment monitoring - Liuyang Zhang; Chaoyan Hu; Yanzi Zhao; Sihua Li; Qian Huang; Long Zhang; Xiaoyan Qu; Bo Lei (Chemical Engineering Journal, 2024)

Lithium isotope systematics in an endorheic saline lacustrine system: Insights from Qinghai Lake, China - Yin Li; Yang-Yang Wang; Fancui Kong; Haicheng Wei; Jack Geary Murphy; Dong-Bo Tan; Jing Chen; Jing Lei; Yigan Lu; Cheng-Long Yu; Yilin Xiao (Applied Geochemistry, 2024)

Effect of pseudorabies virus infection on NMDA receptor expression in mice and its role in immunosuppression - Meng-Die Gong; Jiang-Yu Long; Wen-Bo Xu; Chong-Yin Huang; Si-Yu Meng; Xiao-Tong Zhang; Zhao-Ying Liu (Veterinary Microbiology, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Pyrolysis and oxidation mechanisms of ethylene and ethanol blended fuel based on ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Biao Chen; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2024)

Luminol-Eu3+-Gd3+-functionalized mesoporous silica for ultrasensitive detection of tetracycline antibiotics and smartphone-assisted sensing analysis - Long-Hui Duan; Jing Wang; Hai-Bo Liu (Food Chemistry, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

A phase field framework to model acid fracture propagation with hydro-mechano-reactive flow coupling - Qingdong Zeng; Taixu Li; Piyang Liu; Long Bo; Chi Yao; Jun Yao (Computers and Geotechnics, 2024)

Competitive design of weakly solvated electrolyte enables stable cycling of 4.6 V LiCoO2 - Long Chen; Xiaozhi Jiang; Maohui Bai; Bowen Zhu; Mengran Wang; Bo Hong; Yanqing Lai; Jie Li (Chemical Engineering Journal, 2024)

Zwitterionic adsorbents derived from self-Exfoliated ionic covalent organic frameworks for efficient Co-Removal of anionic and cationic radionuclides - Zhengdong Ouyang; Xiaofeng Li; Jie Zhang; Bo Li; Honghan Long; Yingdan Zhang; Kaifu Yu; Yang Li; Lijian Ma (Chemical Engineering Journal, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Numerical and Field Investigations of Dynamic Failure Caused by Mining-Induced Tremor Based on Focal Mechanism - Zhi-Long He; Yan-Bo Zhang; Cai-Ping Lu; Qi Wang; Xu-Long Yao; Jie-Fang Song; You-Bang Lai (Rock Mechanics and Rock Engineering, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Real-time monitoring of maize phenology with the VI-RGS composite index using time-series UAV remote sensing images and meteorological data - Ziheng Feng; Zhida Cheng; Lipeng Ren; Bowei Liu; Chengjian Zhang; Dan Zhao; Heguang Sun; Haikuan Feng; Huiling Long; Bo Xu; Hao Yang; Xiaoyu Song; et al. (Computers and Electronics in Agriculture, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

Numerical predictions of progressive collapse in reinforced concrete beam-column sub-assemblages: A focus on 3D multiscale modeling - Xu Long; Percy M. Iyela; Yutai Su; Meklit M. Atlaw; Shao-Bo Kang (Engineering Structures, 2024)

Dynamically reversible cross-linked polymer electrolytes with highly ionic conductivity for dendrite-free lithium metal batteries - Xiaowei Wang; Meihuang Wang; Hongli Chen; Yayun Zhang; Bo Niu; Liying Tian; Donghui Long (Chemical Engineering Journal, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

MOF-derived CoP/C catalyst for efficient dibenzothiophene hydrodesulfurization - Liang-Liang Zhang; Kai-Xuan Yang; Cai-Long Xue; Wan-Xi Li; Bo-Qiong Li; Yi-En Du; Yong-Qiang Chen; Ya-Jie Liu (Fuel, 2024)

Self-assembled complexing agent assisted chemical bath deposition of SnOX enabled highly efficient perovskite solar cells - Long Dong; Pin Lv; Benjia Zhu; Yanqing Zhu; Min Hu; Feifei Yang; Bo Zhang; Yi-Bing Cheng; Mi Xu; Jianfeng Lu (Chemical Engineering Journal, 2024)

Facilitating the fabrication of diverse bio-based nanomaterials from bamboo using one-pot hydrated deep eutectic solvent pretreatment - Xin-Yi Hui; Cheng Zuo; Ying Xu; Bo Wang; Jia-Long Wen; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Recycled lower oceanic crust signal in early Jurassic A1-type granites, South China: Implications for flat-slab subduction and mantle heterogeneity in the continental back-arc region - Bo Yan; Wu-Xian Li; Xiao-Long Huang; Ji-Hua Tao (Chemical Geology, 2024)

Reactions of sulfur trioxide with hypochlorous acid catalyzed by water in gas phase and at the air-water nanodroplet interface in the atmosphere: An important sink for hypochlorous acid - Qiao Gao; Zegang Dong; Bo Long (Atmospheric Environment, 2024)

A highly specific and ultrasensitive approach to detect Prymnesium parvum based on RPA-CRISPR-LbaCas12a-LFD system - Hai-Long Huang; Ning-Jian Luo; Wei-Zhong Chen; Xing-Wei Wang; Cheng-Xu Zhou; Hai-Bo Jiang (Analytica Chimica Acta, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Establishment and characterization of the PDAC-X3 cell line: a novel Chinese-origin pancreatic ductal adenocarcinoma cell line - Changpeng Chai; Huan Tang; Xin Miao; Yuanhui Su; Lu Li; Cheng Yu; Jianfeng Yi; Zhenzhen Ye; Long Miao; Bo Zhang; Zhengfeng Wang; Wei Luo; et al. (Human Cell, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Surface engineering strategy for MXene to tailor electromagnetic wave absorption performance - Yunfei He; Qiang Su; Dongdong Liu; Long Xia; Xiaoxiao Huang; Di Lan; Yanan Liu; Yudong Huang; Bo Zhong (Chemical Engineering Journal, 2024)

Two new cytotoxic diterpenoid alkaloids from Delphinium grandiflorum - Ze-dong Nan; Ying Shang; Chao-fan Deng; Yi-dong Zhu; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Phytochemistry Letters, 2024)

Temperature-Dependent NiFeAl catalysts for efficient microwave-assisted catalytic pyrolysis of polyethylene into value-added hydrogen and carbon nanotubes - Zhe Zhang; Huan Chen; Wenheng Hu; Meng Xie; Yukun Pan; Bo Niu; Dengle Duan; Lu Ding; Donghui Long; Yayun Zhang (Fuel, 2024)

Suppression of photoreactivation of E. coli by excimer far-UV light (222 nm) via damage to multiple targets - Zi-Bo Jing; Wen-Long Wang; Yu-Jia Nong; Lu Peng; Zi-Chen Yang; Bei Ye; Min-Yong Lee; Qian-Yuan Wu (Water Research, 2024)

Mechanical properties of partially bonded rock anchors in squeezing large-deformation soft rock tunnels - Wei Yu; Bo Wang; Jinwei Liu; Long Chen; Xin Zi (Tunnelling and Underground Space Technology, 2024)

Studies on the mechanism of the contact toxicity of carvone against Tribolium castaneum - Jun-Yu Liang; Zhi-Bo Hou; Xiao-Han Zhang; Qian Zhang; Zhen-jia Ma; Wei-Bao Kong; Jun-Long Wang; Ji Zhang; Feng Zhou (Journal of Stored Products Research, 2024)

Removal of Cu(II) by sodium hexametaphosphate and nano zero-valent iron modified calcium bentonite: characteristic, adsorption performance and mechanism - Hao Qin; Long Xu; Lin Qin; Bo Kang; Fusheng Zha; Qiao Wang; Kai Huang (Journal of Environmental Management, 2024)

High-Precision 3D reconstruction and quantitative structure description: Linking microstructure to macroscopic heat transfer of aerogels - Xiaxi Xu; Qingfu Huang; Bingbin Chen; Bo Niu; Yayun Zhang; Donghui Long (Chemical Engineering Journal, 2024)

Detailed insights of polydimethylsiloxane (PDMS) degradation mechanism via ReaxFF MD and experiments - Junjie Wang; Guixiang Li; Zhe Zhang; Qingfu Huang; Bo Niu; Yayun Zhang; Donghui Long (Chemical Engineering Journal, 2024)

Multimedia distribution, dynamics, and seasonal variation of PAHs in Songhua wetland: Implications for ice-influenced conditions - Bo Meng; Xi-Ze Min; Meng-Yuan Xiao; Wen-Xi Xie; Wen-Long Li; Ming-Gang Cai; Hang Xiao; Zi-Feng Zhang (Chemosphere, 2024)

Ferrate(VI) assists in reducing cytotoxicity and genotoxicity to mammalian cells and organic bromine formation in ozonated wastewater - Ye Du; Tong Liu; Lu-Lin Yang; Zhi-Min Song; Xin Dai; Wen-Long Wang; Bo Lai; Qian-Yuan Wu (Water Research, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Over-expansion cycle as clean combustion strategy applied to a marine low-speed dual fuel engine - Jianlin Cao; Yang Wang; Dongsheng Dong; Fuxing Wei; Heng Zhang; Longlong Jiang; Pengbo Dong; Bo Li; Ge Xiao; Wuqiang Long (Journal of Cleaner Production, 2024)

A study of guar gum derivatives as green kinetic hydrate inhibitors - Bo Liu; Xiang-Long Ding; Yi-Ming Dai; Li Wan (Journal of Environmental Chemical Engineering, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Diammonium cation pre-intercalation into inorganic framework for efficient Dion-Jacobson perovskite solar cells - Feng Long; Yuhan Guo; Ligang Yuan; Hao Yin; Yiran Tao; Zegang Jiang; Shimin Peng; Bo Wu; Keyou Yan; Ming Liu; Xinhui Lu; Weiwei Meng; et al. (Chemical Engineering Journal, 2024)

Dual fluorescence induced thermally activated delayed fluorescence materials based on 2,4-Diphenylthieno[3,2-d]pyrimidine with an efficient single-molecular white electroluminescence - Xiangbin Tian; Shu Xiao; Jing Sun; Jiakui Yan; Guozheng Li; Bo Zhao; Yanqin Miao; Long Wang; Hua Wang; Dongge Ma (Chemical Engineering Journal, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Predicting Drug-Drug Interactions Involving Rifampicin Using a Semi-mechanistic Hepatic Compartmental Model - Jingxi Li; Xue Li; Keheng Wu; Sihui Long; Youni Zhao; Xiong Jin; Mengjun Zhang; Xinyi Wu; Zhijun Huang; Zhou Zhou; Jack Liu; Bo Liu (Pharmaceutical Research, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

An anomalous rollback process of Mesozoic flat-slab subduction in South China - Bo Yan; Wu-Xian Li; Xiao-Long Huang; Yang Yu; Ji-Hua Tao (Tectonophysics, 2024)

Intelligent multi-objective optimization of 3D printing low-carbon concrete for multi-scenario requirements - Song-Yuan Geng; Qi-Ling Luo; Bo-Yuan Cheng; Li-Xiao Li; Dong-Chang Wen; Wu-Jian Long (Journal of Cleaner Production, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Global occurrence characteristics, drivers, and environmental risk assessment of microplastics in lakes: A meta-analysis - Long Chen; Shenglu Zhou; Qi Zhang; Bo Su; Qiqi Yin; Mengmeng Zou (Environmental Pollution, 2024)

Enhancing safety through the biodegradable pesticide microcapsules produced via melt emulsification and interfacial polymerization - Long Chen; Weiqun Zhang; Huan Du; Xiquan Ding; Liang Li; Hongyan Chen; Fei Gao; Bo Cui; Jinming Gao; Haixin Cui; Yishan Yao; Zhanghua Zeng (Chemical Engineering Journal, 2024)

SbMYC2 mediates jasmonic acid signaling to improve drought tolerance via directly activating SbGR1 in sorghum - Guangling Wang; Yufei Long; Xueying Jin; Zhen Yang; Lingyan Dai; Yonghua Yang; Guihua Lu; Bo Sun (Theoretical and Applied Genetics, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

The evaluation of EMI characteristics of 4G-IMT system on FAST around its RQZ - Jian Wang; Yi-Bo Zhao; Cheng Yang; Ya-Fei Shi; Yu-Long Hao; Hai-Yan Zhang; Jian-Min Sun; Ding-Ling Luo (Advances in Space Research, 2024)

Sedimentary record of microplastics in coastal wetland, eastern China - Yujie Zhou; Shenglu Zhou; Sophia Shuang Chen; Yan Li; Long Chen; Qi Zhang; Bo Su; Teng Wang (Water Research, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Numerical investigation of a semi-submersible platform interacting with steep waves using a fully nonlinear method - Zi-Lin Zhang; Shi-Li Sun; Bo-Yu Chen; Hui-Long Ren (Ocean Engineering, 2024)

Analysis of forestry management based on dynamic life cycle assessment of biogenic carbon: A case study of a forestry resource-based city in Northeast China - Bo Song; Jin Tang; Feng Long; Yuqing Peng; Fenfen Bi; Yueao Kang; Dayi Qian (Journal of Cleaner Production, 2024)

Catalytic reforming of cellulose pyrolysis volatiles over hierarchical HZSM-5: Mechanism of a protective effect of tetrapropylammonium (TPA+) during alkali treatment - Xin-Bo Pang; Jing-Pei Cao; Nai-Yu Yao; Jing-Ping Zhao; Tian-Long Liu; Shi-Jie Cai; Hong-Yan Wang; Yan-Cheng Hu; Xiao-Yan Zhao (Fuel, 2024)

Petroleum-like fuels with substantially enriched branched iso-paraffins and benzenes via boehmite-assisted pyrolysis of oil shale - Guojing Xu; Zhaoyang Ren; Zhenpeng Wang; Lijie Cui; Jian-Zheng Su; Xiang-Long Meng; Penglei Chen; Peng Li; Nannan Wang; Xiang Hao; Bo Guan (Fuel, 2024)

Neoproterozoic tectonic evolution and proto-basin of the Yangtze Block, China - Yunpeng Dong; Bo Hui; Shengsi Sun; Dengfeng He; Jiaopeng Sun; Feifei Zhang; Chao Cheng; Zhao Yang; Xiaohui Shi; Rutao Zang; Xiaoping Long; Guowei Zhang (Earth-Science Reviews, 2024)

Tracking of Stem Cells in Chronic Liver Diseases: Current Trends and Developments - Jin-Long He; Yi-Xian You; Xiong Pei; Wei Jiang; Qing-Min Zeng; Bin Chen; Yong-Hong Wang; En-Qiang Chen; Hong Tang; Xiu-Feng Gao; Dong-Bo Wu (Stem Cell Reviews and Reports, 2024)

C. burnetii meningitis with stroke causing fever, headache and peripheral facial paralysis - Shanyu Pi; Bo Xiao; Hongyu Long (Acta Neurologica Belgica, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Enhancing Zn2+ diffusion for dendrite-free zinc anodes via a robust zincophilic clay mineral coating - Mengjiao Liu; Anjun Hu; Zhongfu Yan; Jiahao Chen; Miao He; Bo Zhou; Yu Pan; Yining Fan; Daojiang Gao; Jianping Long (Chemical Engineering Journal, 2024)

Thermo-responsive liposome nano-vesicles for co-delivery of emamectin benzoate and nitenpyram with synergistic pest control - Qian Du; Xi-Quan Ding; Fei Gao; Bo Cui; Ting-Yu Wang; Fang-Yuan Chen; Long Chen; Hong-Yan Chen; Hai-Xin Cui; Yan Wang; Zhang-Hua Zeng (Chemical Engineering Journal, 2024)

Mechanism of Diabatic Heating on Precipitation and the Track of a Tibetan Plateau Vortex over the Eastern Slope of the Tibetan Plateau - Yuanchang Dong; Guoping Li; Xiaolin Xie; Long Yang; Peiwen Zhang; Bo Zeng (Advances in Atmospheric Sciences, 2024)

Trends in the occurrence and accumulation of microplastics in urban soil of Nanjing and their policy implications - Yujie Zhou; Teng Wang; Mengmeng Zou; Qiqi Yin; Zhenyi Jia; Bo Su; Qi Zhang; Long Chen; Shenglu Zhou (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

How is the acceptance of new energy vehicles under the recurring COVID-19 — A case study in China - Yahong Jiang; Qunqi Wu; Bo Chen; Qian Long; Yongchao Song; Jun Yang (Journal of Cleaner Production, 2023)

Investigation on jet controlled diffusion combustion (JCDC) mode applied on a marine large-bore two-stroke engine - Jianlin Cao; Dongsheng Dong; Fuxing Wei; Wuqiang Long; Ge Xiao; Longlong Jiang; Bo Li; Yang Wang (Journal of Cleaner Production, 2023)

Transport of pollutants in groundwater of domestic waste landfills in karst regions and its engineering control technologies - Bo Li; Teng Li; Pan Wu; Lei Yang; Jie Long; Pu Liu; Tao Li (Journal of Environmental Management, 2023)

Quantitative Analysis of Cu(II)-Induced Deterioration Effects on Barrier Performance of Soil-Bentonite Slurry - Fusheng Zha; Hao Qin; Long Xu; Yinbin Shen; Bo Kang; Yuzhao Wu (Water, Air, & Soil Pollution, 2023)

Analysis of the stress field in the reactor vessel of the China Initiative Accelerator Driven System during postulated ULOF and UTOP transients - Zi-Nan Huang; Yun-Xiang Li; Song Li; Bin Xi; You-Peng Zhang; Lu Meng; Di-Si Wang; Bo Liu; Long Gu; Tian-Ji Peng; Lu Zhang; Wei Jiang; et al. (Annals of Nuclear Energy, 2023)

Special topic on EvoDevo: emerging models and perspectives - Hongan Long; Bo Dong (Marine Life Science & Technology, 2023)

Design and experiment of an integrated navigation system for a paddy field scouting robot - Yuyuan Tian; Zhenpeng Mai; Zhiwei Zeng; Yinghu Cai; Jinpeng Yang; Bo Zhao; Xuhua Zhu; Long Qi (Computers and Electronics in Agriculture, 2023)

Proteomic characteristics of six snake venoms from the Viperidae and Elapidae families in China and their relation to local tissue necrosis - Wan-Gang Qin; Zhan-Peng Zhuo; Hao Hu; Mimi Lay; Qian-Qin Li; Jun-Ting Huang; Liang-Bo Zeng; Zi-Jing Liang; Fei Long; Qing Liang (Toxicon, 2023)

Microplastics in agricultural soils on the coastal plain: Spatial characteristics, influencing factors and sources - Yujie Zhou; Zhenyi Jia; Gunghui Zheng; Long Chen; Qi Zhang; Bo Su; Shenglu Zhou (Science of The Total Environment, 2023)

Monoterpenoids from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, 5-lipoxygenase, andcyclooxygenase-2 in vitro - Hao-Dong Yang; Zhi-Shu Tang; Tao-Tao Xue; Huai-Li Xu; Bao-Long Hou; Ya-Ya Zhu; Zeng-Hu Su; Hong-Bo Xu (Phytochemistry, 2023)

Propeller-shaft-hull coupling acoustic radiation characteristics induced by friction self-excitation of the stern bearing - Chang-Gang Lin; Ming-Song Zou; Li-Bo Qi; Can Sima; Ji-Long Chu (Ocean Engineering, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Phosphate recovery using activated sludge cyanophycin: Adsorption mechanism and utilization as nitrogen-phosphorus fertilizer - Jinyu Zeng; Duoduo Chen; Jing Zhu; Caicheng Long; Taiping Qing; Bo Feng; Peng Zhang (Chemical Engineering Journal, 2023)

Chemical functionalization of commercial Pt/C electrocatalyst towards formic acid electrooxidation - Zi-Xin Ge; Bo-Qiang Miao; Xin-Long Tian; Bin He; Yu Chen (Chemical Engineering Journal, 2023)

Manipulation of crystallization nucleation and thermal degradation of PLA films by multi-morphologies CNC-ZnO nanoparticles - Ya-Fang Yan; Xiao-Bo Liang; Yan-Long Feng; Lin-Fang Shi; Rui-Pin Chen; Jian-Zhong Guo; Ying Guan (Carbohydrate Polymers, 2023)

Toxic effects of combined exposure to cadmium and nitrate on intestinal morphology, immune response, and microbiota in juvenile Japanese flounder (Paralichthys olivaceus) - Pengfei Liu; Yingying Wan; Ziyi Zhang; Qing Ji; Jie Lian; Chuanzheng Yang; Xingqiang Wang; Bo Qin; Long zhu; Jiachen Yu (Aquatic Toxicology, 2023)

α-Linolenic acid-regulated testosterone biosynthesis via activation of the JNK-SF-1 signaling pathway in primary rooster Leydig cells - Zhi-Xian Zhao; Ming-Yu Shang; Cheng Long; Xue-Jun Yao; Xiao-Bo Gao; Yong Guo; Xi-Hui Sheng; Xiang-Guo Wang; Kai Xing; Long-Fei Xiao; Xiao-Long Qi (Theriogenology, 2023)

Bioactive ellagitannins and phenylpropanoid glycosides from the seed of Torreya grandis - Xue-Hui Wang; Xiao-Jing Shao; Yi-Ran Jiang; Tian-Tian Bei; Wen-Hui Xu; Bo-Wen Ren; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2023)

Collision avoidance fault-tolerant control for dynamic positioning vessels under thruster faults - Ming-Yang Li; Long-Tao Liu; Wen-Bo Xie; Ji-Tao Li (Ocean Engineering, 2023)

Shelf-life enhancement of bio-inoculants through synergistic effects of encapsulation technology and osmotic protectants - Mi Hu; Ruo-nan Hei; De-jie Guo; Jia Luo; Chao Lu; Wen-long Xu; Zhi-yang Zhang; Qing-bo Xiao; Yan Ma (Journal of Environmental Chemical Engineering, 2023)

Efficient methotrexate adsorption on magnetic-functionalised UiO-66-NH2: Selectivity, mechanisms and recycling - Qiang Bi; Bo Yang; Kun Zhang; Tong Yang; Peng Wang; Long Shi; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Tectonic evolution of the Meso-Tethys Ocean in the Jurassic: Birth, growth, and demise of a missing intra-oceanic arc - Bo-Chuan Zhang; Jian-Jun Fan; An-Bo Luo; Xiao-Wen Zeng; Men-Long Duan; Si-Lin Sun (Gondwana Research, 2023)

Ultrathin zinc-carbon composite anode enabled with unique three-dimensional interpenetrating structure for high-performance aqueous zinc ion batteries - Yuhuan Meng; Lequan Wang; Jiaxi Zeng; Bo Hu; Junming Kang; Yixiang Zhang; Jiajia Zhang; Zedong Zhao; Long Zhang; Hongbin Lu (Chemical Engineering Journal, 2023)

Mechanisms and Functions of Activity-Regulated Cytoskeleton-Associated Protein in Synaptic Plasticity - Yifan Chen; Xiaohu Wang; Bo Xiao; Zhaohui Luo; Hongyu Long (Molecular Neurobiology, 2023)

Chemical constituents of Aspergillus udagawae isolated from the soil of the Xingren coal areas and their antibacterial activities - Xing-Mei Long; Qin-Feng Zhu; Bing Wang; Guang-Gui Chen; Kai-Yu Li; Xun He; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2023)

Investigation on the mechanism of Nb and Si co-doping on low SO3 generation from V-based catalyst during NH3-SCR process - Shuo Feng; Bo Wang; Yuye Xing; Wenwen Kong; Jiao Ma; Chenguang Zhang; Zhaoming Li; Boxiong Shen; Zhuozhi Wang; Long Chen; Jiancheng Yang (Fuel, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Constructing bifunctional porous nanosheets for efficient conversion of waste plastics into valuable hydrogen and carbons - Meng Xie; Hai Xu; YiXuan Wang; Helin Pan; Dengle Duan; Bo Niu; Donghui Long; Yayun Zhang (Chemical Engineering Journal, 2023)

Gypenosides suppress hepatocellular carcinoma cells by blocking cholesterol biosynthesis through inhibition of MVA pathway enzyme HMGCS1 - Man-Yu Xiao; Fang-Fang Li; Peng Xie; Yan-Shuang Qi; Jin-Bo Xie; Wen-Jing Pei; Hao-Tian Luo; Mei Guo; Yu-Long Gu; Xiang-Lan Piao (Chemico-Biological Interactions, 2023)

The induction of ferroptosis by KLF11/NCOA4 axis: the inhibitory role in clear cell renal cell carcinoma - Zi-Qi Zhou; Xi Lv; Shi-Bo Liu; Hong-Chen Qu; Qing-Peng Xie; Long-Feng Sun; Gang Li (Human Cell, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

Adsorption behavior of antibiotics with different structures onto vivianite in the presence of dissolved organic matter during the phosphorus recovery process - Wang-Xiao Jia; Wen-Qiang Li; Zhi-Hui Xie; Pu-Can Guo; Zhi-Long Ye; Zhao-Kun Xiong; Chuan-Shu He; Bo Lai (Chemical Engineering Journal, 2023)

Neuron-Derived Exosomes Promote the Recovery of Spinal Cord Injury by Modulating Nerve Cells in the Cellular Microenvironment of the Lesion Area - Yi Xu; Zheng-huan Zhu; Xu Xu; Hai-tao Sun; Hong-ming Zheng; Jin-long Zhang; Hong-hai Wang; Jia-Wei Fang; Ya-zheng Liu; Lin-ling Huang; Zhi-wen Song; Jin-bo Liu (Molecular Neurobiology, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Spatial distribution, pollution characteristics, and health risks of antibiotic resistance genes in China: a review - Zhixiang Xu; Yue Jia; Bin Huang; Dimeng Zhao; Xin Long; Siyuan Hu; Caiqing Li; Guohua Dao; Bo Chen; Xuejun Pan (Environmental Chemistry Letters, 2023)

Conductivity characteristics of landslide considering porosity, saturation, temperature and ion concentration - Bo-bo Xiong; Shi-jie Yang; Bing-qin Zhao; Xiao-chun Lu; Bin Tian; Cheng Li; Xuan-xuan Wu; Xiao-long Tu (Journal of Mountain Science, 2023)

Effect of the random distribution of gravel particles on the mechanical behaviors of conglomerate - Jun Wei; Hualin Liao; Bin Huang; Ning Li; Hongjun Liang; Bo Zhou; Quan Zhang; Long Chen; Hui Feng (Arabian Journal of Geosciences, 2023)

Molecular network technology for discovering new alkaloids glycosides from Goji berry - Jian Ma; Xiao-Li Ma; Zhi-Bo Jiang; Ze-Dong Nan; Chong-Long Li (Brazilian Journal of Botany, 2023)

Aerobic granular sludge formation and stability in enhanced biological phosphorus removal system under antibiotics pressure: Performance, granulation mechanism, and microbial successions - Long Cheng; Mingyu Wei; Qixing Hu; Bingtang Li; Bo Li; Wenjia Wang; Zaidun Naji Abudi; Zhiquan Hu (Journal of Hazardous Materials, 2023)

Behaviour of bamboo scrimber I-beam-box-column connections under static loads - Shao-Bo Kang; Jie-Xin Ding; Jun Xiong; Shu-Rong Zhou; Bin Long (Engineering Structures, 2023)

Unveiling the structure–activity relationships of ofloxacin degradation by Co3O4-activated peroxymonosulfate: From microstructures to exposed facets - Bo Li; Huan-Yan Xu; Yu-Long Liu; Yue Liu; Yan Xu; Si-Qun Zhang (Chemical Engineering Journal, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Grain boundary capacitance effect in Iron-based magnetic composites for superior C-band microwave absorption - Chengshuai Shao; Chunyan Ding; Yu Liu; Yu Ma; Long Zhang; Xiaozhen Ren; Songsong Wu; Bo Zhong; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2023)

Toward a better understanding of uncertainty for satellite precipitation products over complex terrain with sparse rain gauge data - Yingying Gai; Xunjian Long; Zhihao Wei; Xinxin Sui; Bo Jiang; Xi Chen; Dingfeng Yu; Shengguang Qin; Yaokui Cui (Atmospheric Research, 2023)

Characteristics of inverse dispersion curve of Rayleigh wave in pavement shallow structure with engineering application - Bo Yang; Chao Shen; Yuewen Tang; Meng Zhang; Youming Long (Journal of Applied Geophysics, 2023)

Coupling effect of fiber reinforcement and MICP stabilization on the tensile behavior of calcareous sand - Dian-Long Wang; Chao-Sheng Tang; Xiao-Hua Pan; Bo Liu; Bin Shi (Engineering Geology, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Optimization of natural deep eutectic solvents extraction of flavonoids from Xanthoceras sorbifolia Bunge by response surface methodology - Zhi-ao Feng; Dan Yang; Jin-jin Guo; Yu-kun Bo; Long-shan Zhao; Ming An (Sustainable Chemistry and Pharmacy, 2023)

Trichosanthes kirilowii Maxim seed kernel oil: The optimization of ultrasound-assisted extraction and evaluation of its potential as a novel biodiesel feedstock - Hai-long Zhang; Zhi-xian Wang; Shan-shan Wei; Xiao-qiong Liu; Jun-Bo He; Wei-nong Zhang; Jing Du (Sustainable Chemistry and Pharmacy, 2023)

Sluggish lithium isotopic response of continental intraplate basalts to recycled sedimentary carbonate - Yang-Yang Wang; Cheng-Long Yu; Dong-Bo Tan; He Sun; Hai-Ou Gu; Fengtai Tong; Li-Hui Chen; Yilin Xiao (Lithos, 2023)

The diverging epigenomic landscapes of honeybee queens and workers revealed by multiomic sequencing - Yong Zhang; Xu Jiang He; Andrew B. Barron; Zhen Li; Meng Jie Jin; Zi Long Wang; Qiang Huang; Li Zhen Zhang; Xiao Bo Wu; Wei Yu Yan; Zhi Jiang Zeng (Insect Biochemistry and Molecular Biology, 2023)

Monoacylglycerol lipase from marine Geobacillus sp. showing lysophospholipase activity and its application in efficient soybean oil degumming - Xuan Liu; Weifei Wang; Zexin Zhao; Long Xu; Bo Yang; Dongming Lan; Yonghua Wang (Food Chemistry, 2023)

An investigation of hydraulic fracture propagation in multi-layered formation via the phase field method - Qingdong Zeng; Long Bo; Wenzheng Liu; Zhaoqin Huang; Jun Yao (Computers and Geotechnics, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Preliminary Investigation on Marine Radar Oil Spill Monitoring Method Using YOLO Model - Bo Li; Jin Xu; Xinxiang Pan; Rong Chen; Long Ma; Jianchuan Yin; Zhiqiang Liao; Lilin Chu; Zhiqiang Zhao; Jingjing Lian; Haixia Wang (Journal of Marine Science and Engineering, 2023)
Due to the recent rapid growth of ocean oil development and transportation, the offshore oil spill risk accident probability has increased unevenly. The marine oil spill poses a great threat to the development of coastal cities. Therefore, effective and reliable technologies must be used to monitor oil spills to minimize disaster losses. Based on YOLO deep learning network, an automatic oil spill detection method was proposed. The experimental data preprocessing operations include noise reduction, gray adjustment, and local contrast enhancement. Then, real and synthetically generated marine radar oil spill images were used to make slice samples for training the model in the YOLOv5 network. The detection model can identify the effective oil spill monitoring region. Finally, an adaptive threshold was applied to extract the oil slicks in the effective oil spill monitoring regions. The YOLOv5 detection model generated had the advantage of high efficiency compared with existing methods. The offshore oil spill detection method proposed can support real-time and effective data for routine patrol inspection and accident emergency response.

Estimating characteristic coefficient of vertical leaf nitrogen profile within wheat canopy from spectral reflectance - Heli Li; Guijun Yang; Huiling Long; Haikuan Feng; Bo Xu; Chunjiang Zhao (Computers and Electronics in Agriculture, 2023)

Flexible guided anti-collision device for bridge pier protection against ship collision: Numerical simulation and ship collision field test - Fei Wang; Hui-Juan Chang; Bo-Han Ma; Yong-Gang Wang; Li-Ming Yang; Jun Liu; Xin-Long Dong (Ocean Engineering, 2023)

Identifying the evolution of primary oxidation mechanisms and pollutant degradation routes in the electro-cocatalytic Fenton-like systems - Xianhu Long; Hongle Shi; Rongfu Huang; Lingyun Gu; Yang Liu; Chuan-shu He; Ye Du; Zhaokun Xiong; Wen Liu; Bo Lai (Journal of Hazardous Materials, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

An internally damped inertial platform for marine gravimetry and a test case in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

A marine gravimeter based on electromagnetic damping and its tests in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

Ferroptosis-related NFE2L2 and NOX4 Genes are Potential Risk Prognostic Biomarkers and Correlated with Immunogenic Features in Glioma - Li Lin; Xiaona Li; Shunda Zhu; Qingshan Long; Yongzhen Hu; Liyang Zhang; Zexin Liu; Bo Li; Xuesong Li (Cell Biochemistry and Biophysics, 2023)
Ferroptosis is a newfound mode of regulated cell death that may have potential to associate with prognostic or diagnostic factors in glioma. In this research, 5 genes related to glioma were screened through the FerrDb database, and we analyzed the combination between genes and glioma of survival and prognosis via TCGA, GEPIA, TIMER, and other databases. Survival curve and prognostic analysis showed that the overexpression of NFE2L2 and NOX4 , respectively, has a remarkable link with a worse prognosis in glioma. Then, the association between the expression of the two genes and tumor-infiltrating immune cells level was explored based on the GSCA, and the immunity of NFE2L2 and NOX4 based on the TISIDB database was also investigated. In glioma, especially GBM, there is a strong association between gene expression and immune infiltration, even in macrophages, nTreg, and Th2 cells, which play immunosuppressive functions in TME. In conclusion, these results indicate that NFE2L2 and NOX4 could be risk prognosis biomarkers in glioma, and they bound up with immune infiltration and tumor immunity in tumorigenesis.

Application of logistic regression model for hazard assessment of landslides caused by the 2012 Yiliang Ms 5.7 earthquake in Yunnan Province, China - Jia-le Jin; Yu-long Cui; Chong Xu; Jun Zheng; Hai-bo Miao (Journal of Mountain Science, 2023)

Transient analysis of the CiADS reactor core loaded with nitride fuel - Bo Liu; Song Li; You-Peng Zhang; Janne Wallenius; Bin Xi; Long Gu; Jin-Yang Li; Di-Si Wang; Wei Jiang; Lu Zhang (Annals of Nuclear Energy, 2023)

Controlling factors on the charging process of oil and gas in the eastern main sub-sag of the Baiyun Sag, Zhujiang River (Pearl River) Mouth Basin - Cong Chen; Xiangtao Zhang; Guangrong Peng; Zulie Long; Baojun Liu; Xudong Wang; Puqiang Zhai; Bo Zhang (Acta Oceanologica Sinica, 2023)

β‐diversity in temperate grasslands is driven by stronger environmental filtering of plant species with large genomes - Hai‐Yang Zhang; Xiao‐Tao Lü; Cun‐Zheng Wei; Jeff R. Powell; Xiao‐Bo Wang; Ding‐Liang Xing; Zhu‐Wen Xu; Huan‐Long Li; Xing‐Guo Han (Ecology, 2023)
Elucidating mechanisms underlying community assembly and biodiversity patterns is central to ecology and evolution. Genome size (GS) has long been hypothesized to potentially affect species' capacity to tolerate environmental stress and might therefore help drive community assembly. However, its role in driving β‐diversity (i.e., spatial variability in species composition) remains unclear. We measured GS for 161 plant species and community composition across 52 sites spanning a 3200‐km transect in the temperate grasslands of China. By correlating the turnover of species composition with environmental dissimilarity, we found that resource filtering (i.e., environmental dissimilarity that includes precipitation, and soil nitrogen and phosphorus concentrations) affected β‐diversity patterns of large‐GS species more than small‐GS species. By contrast, geographical distance explained more variation of β‐diversity for small‐GS than for large‐GS species. In a 10‐year experiment manipulating levels of water, nitrogen, and phosphorus, adding resources increased plant biomass in species with large GS, suggesting that large‐GS species are more sensitive to the changes in resource availability. These findings highlight the role of GS in driving community assembly and predicting species responses to global change.

Mass transfer enhancement of air sparging on VOCs contaminated low-permeability soil by establishing pressure gradient - Long Xu; Xinyi Hu; Fusheng Zha; Heyong Kang; Lixing Fang; Bo Kang; Chengfu Chu; Chengbin Yang (Chemosphere, 2023)

Airflow characteristics of rotorcraft plant protection UAV operating in rice fields - Gangao Fan; Zhijie Liu; Yijuan Qin; Bo Long; Huifen Li; Jiyu Li (Biosystems Engineering, 2023)

Risks of applying mobilising agents for remediation of arsenic-contaminated soils: Effects of dithionite–EDTA and citric acid on arsenic fractionation, leachability, oral bioavailability/bioaccessibility and speciation - Xiao-Chen Chen; Cong-Cong Yao; Ao Wang; Zeng-Di Zhang; Long-Zhao Chen; Jian-Yu Zhang; Xian-Hua Liu; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Distribution of Li, Ga, Nb, and REEs in coal as determined by LA-ICP-MS imaging: A case study from Jungar coalfield, Ordos Basin, China - Bo Jiu; Wenhui Huang; Baruch Spiro; Ruilin Hao; Nana Mu; Long Wen; Huidi Hao (International Journal of Coal Geology, 2023)

Multiple-objective optimization of Jet Controlled Compression Ignition (JCCI) mode with dual-direct injection in a high-speed light-duty engine - Bo Li; Jian Wang; Heng Zhang; Liyun Fan; Xianyin Leng; Wuqiang Long; Ge Xiao (Fuel, 2023)

Bioaccumulation and emission of organophosphate esters in plants affecting the atmosphere's phosphorus cycle - Shengxing Long; Paul B. Hamilton; Bo Fu; Jing Xu; Luchao Han; Xinhao Suo; Yuqin Lai; Guofeng Shen; Fuliu Xu; Bengang Li (Environmental Pollution, 2023)

Liquid flow and breakage behaviors of two liquid jets impacting on the wire mesh with different impinging angles - Zhong-Bo Sun; Hai-Long Liao; Li-Hua Wang; Lan Jiang; Xin Zhang; Bao-Ju Wang; Guang-Wen Chu; Yong Luo (Chemical Engineering Journal, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Portal vein tumor thrombosis in hepatocellular carcinoma: molecular mechanism and therapy - Xing-Hao Zhou; Jing-Ru Li; Tang-Hui Zheng; Hong Chen; Chen Cai; Sheng-Long Ye; Bo Gao; Tong-Chun Xue (Clinical & Experimental Metastasis, 2023)

Investigation on swelling characteristics of GMZ bentonite with different initial water contents - Bo Chen; Fan Peng; Long Zhang; De'an Sun (Annals of Nuclear Energy, 2023)

Different dissolved oxygen levels drive polyhydroxyalkanoate biosynthesis from hydrolyzed polyacrylamide-containing oil sludge - Lanmei Zhao; Jian Liu; Long Meng; Dong Zhao; Bo Wang (Process Safety and Environmental Protection, 2023)

Association of whole blood metals/metalloids with severity in sepsis patients: A prospective, single-center, pilot study - Bo Zhang; Qing Yang; Xu Wang; Bingmei Jia; Liming Cheng; Hao-Long Zeng (Journal of Trace Elements in Medicine and Biology, 2023)

Production of hydrocarbon-rich bio-oil from catalytic pyrolysis of waste cooking oil over nickel monoxide loaded corn cob-derived activated carbon - Peng Li; Bo Niu; Helin Pan; Yayun Zhang; Donghui Long (Journal of Cleaner Production, 2023)

Performance characteristics of a two-stroke low speed engine applying ammonia/diesel dual direct injection strategy - Zhenxian Zhang; Wuqiang Long; Pengbo Dong; Hua Tian; Jiangping Tian; Bo Li; Yang Wang (Fuel, 2023)

Effect of sequential thermal dissolution on the structure and pyrolysis characteristics of Naomaohu lignite - Xiao-Bo Hu; Hao Xu; Wen-Long Mo; Xing Fan; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Hong-Yu Mi; Ya-Ya Ma; Xian-Yong Wei (Fuel, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

The Jiamusi Block: A hinge of the tectonic transition from the Paleo-Asian Ocean to the Paleo-Pacific Ocean regimes - Gong-Yu Li; Jian-Bo Zhou; Long Li (Earth-Science Reviews, 2023)

An approach to the high efficient exploitation of nature gas hydrate and carbon sequestration via injecting CO2/H2 gas mixture with varying composition - Bo-Jian Cao; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Ming-Long Wang; Meng-Ya Niu; Jing-Yu Kan; Chang-Yu Sun; Dao-Yi Chen; Guang-Jin Chen (Chemical Engineering Journal, 2023)

Efficient and selective gold recovery from e-waste by simple and easily synthesized covalent organic framework - Shouchao Zhong; Yue Wang; Tao Bo; Jiahui Lan; Zeyu Zhang; Lang Sheng; Jing Peng; Long Zhao; Liyong Yuan; Maolin Zhai; Weiqun Shi (Chemical Engineering Journal, 2023)

Advanced layered oxide cathodes for sodium/potassium-ion batteries: Development, challenges and prospects - Zhi-Xiong Huang; Zhen-Yi Gu; Yong-Li Heng; Edison Huixiang Ang; Hong-Bo Geng; Xing-Long Wu (Chemical Engineering Journal, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Robust MXene adding enables the stable interface of silicon anodes for high-performance Li-ion batteries - Jie Tang; Fuzhong Wu; Xinyi Dai; Jiawang Zhou; Huixia Pang; Xingyu Duan; Bo Xiao; Dongjia Li; Junliang Long (Chemical Engineering Journal, 2023)

Solvothermal synthesis and applications of micro/nano carbons: A review - Yan Huo; Shijian Xiu; Long-Yue Meng; Bo Quan (Chemical Engineering Journal, 2023)

Regeneration of textile sludge into Cu8S5 decorated N, S self-doped interconnected porous carbon as an advanced bifunctional electrocatalyst for overall water splitting - Yinglin Zhang; Long Chen; Bo Yan; Fuping Zhang; Yulin Shi; Xuhong Guo (Chemical Engineering Journal, 2023)

Groundwater Quality Evaluation and Analysis Technology Based on AHP-EWM-GRA and Its Application - Menghua Li; Bo Li; Jingyan Chu; Huang Wu; Zhicheng Yang; Juan Fan; Lei Yang; Pu Liu; Jie Long (Water, Air, & Soil Pollution, 2023)

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis - Long Liu; Feng-Ming Yan; Chen-Chen Zhao; Li-Juan Su; Qiu-Ying Huang; Qing-Bo Tang (Journal of Pest Science, 2023)
Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1 , drive social immunity in insect colonies is still unknown. Here, we used a ‘host–pathogen’ system (host: Reticulitermes chinensis ; pathogen: Metarhizium anisopliae ) to explore the impact of miRNAs on social immunity in termite colonies. We found that RNAi-mediated silencing of Dicer-1 led to decreased miRNA concentration, significantly inhibited carbohydrate and energy metabolism and affected other life processes, such as the immune response and oxidation–reduction reactions, in whole body of the termite. In behavioural defence, silencing Dicer-1 significantly diminished defensive social behaviours such as locomotion, grooming, cannibalism and burial in termite groups when encountering fungal contamination. In physiological defence, Dicer-1 silencing and miR-71-5 stimulation resulted in significantly decreased antifungal activities of termites. Furthermore, both Dicer-1 -silenced and miR-71-5 stimulant-treated termite groups exhibited a high level of mortality during fungal contamination. Our findings demonstrated the important role of miRNAs in shaping social immunity in termite colonies, providing insights necessary to understand the potential mechanisms underlying behavioural and physiological disease defences in insects and hence laying the groundwork for miRNA-based pest control.

Effect of polyaspartic acid on soil water storage, soil microbial diversity, cotton yield and fiber quality - Wen-long Liu; Jian-Bo Zhao; Hong Zeng; Chuan-xing Wan (Archives of Microbiology, 2023)

Ptercresions A-C: three new terpenes with hepatoprotective activity from Pteris cretica L - Jianping Hu; Shiping Liu; Ying Long; Ning Tao; Bo Yang; Liyong Zhang (Natural Product Research, 2022)

Water consumption prediction and influencing factor analysis based on PCA-BP neural network in karst regions: a case study of Guizhou Province - Zhicheng Yang; Bo Li; Huang Wu; MengHua Li; Juan Fan; Mengyu Chen; Jie Long (Environmental Science and Pollution Research, 2022)

Marine Radar Oil Spill Extraction Based on Texture Features and BP Neural Network - Rong Chen; Baozhu Jia; Long Ma; Jin Xu; Bo Li; Haixia Wang (Journal of Marine Science and Engineering, 2022)
Marine oil spills are one of the major threats to marine ecological safety, and the rapid identification of oil films is of great significance to the emergency response. Marine radar can provide data for marine oil spill detection; however, to date, it has not been commonly reported. Traditional marine radar oil spill research is mostly based on grayscale segmentation, and its accuracy depends entirely on the selection of the threshold. With the development of algorithm technology, marine radar oil spill extraction has gradually come to focus on artificial intelligence, and the study of oil spills based on machine learning has begun to develop. Based on X-band marine radar images collected from the Dalian 716 incident, this study used image texture features, the BP neural network classifier, and threshold segmentation for oil spill extraction. Firstly, the original image was pre-processed, to eliminate co-channel interference noise. Secondly, texture features were extracted and analyzed by the gray-level co-occurrence matrix (GLCM) and principal component analysis (PCA); then, the BP neural work was used to obtain the effective wave region. Finally, threshold segmentation was performed, to extract the marine oil slicks. The constructed BP neural network could achieve 93.75% classification accuracy, with the oil film remaining intact and the segmentation range being small; the extraction results were almost free of false positive targets, and the actual area of the oil film was calculated to be 42,629.12 m2. The method proposed in this paper can provide a reference for real-time monitoring of oil spill incidents.

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Numerical simulation on flow field, wind erosion and sand sedimentation patterns over railway subgrades - Kai Zhang; Li-ming Zhao; Hai-long Zhang; Ao-jun Guo; Bo Yang; Sheng Li (Journal of Mountain Science, 2022)

Antibacterial activities of the chemical constituents of Schizophyllum commune MST7-3 collected from coal area - Guang-Gui Chen; Qin-Feng Zhu; Xing-Mei Long; Qian Lu; Kai-Yu Li; Qian Chen; Meng Zhou; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2022)

Spatiotemporal variations and structural characteristics of carbon emissions at the county scale: a case study of Wu’an City - Zhi Long; Jiaxing Pang; Shuaike Li; Jingyi Zhao; Ting Yang; Xingpeng Chen; Zilong Zhang; Yingqi Sun; Lixia Lang; Ningfei Wang; Huiying Shi; Bo Wang (Environmental Science and Pollution Research, 2022)

Interdecadal change in the influence of El Niño in the developing stage on the central China summer precipitation - Lin Chen; Gen Li; Shang-Min Long; Chujie Gao; Zhiyuan Zhang; Bo Lu (Climate Dynamics, 2022)

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

Exogenous Melatonin Improves the Growth of Rice Seedlings by Regulating Redox Balance and Ion Homeostasis Under Salt Stress - Long Wei; Haiyan Zhao; Baoxiang Wang; Xinyi Wu; Rujia Lan; Xu Huang; Bo Chen; Gang Chen; Chaoqiang Jiang; Jinlan Wang; Yan Liu; Qingsong Zheng (Journal of Plant Growth Regulation, 2022)

Experimental study of energy and frequency characteristics of acoustic emissions induced from tensile and shear cracks in tunnel rockburst process - Yan-Bo Zhang; Peng Liang; Xu-Long Yao; Lin Sun; Bao-Zhu Tian; Xiang-Xin Liu (European Journal of Environmental and Civil Engineering, 2022)

Glycosides from Buddleja officinalis with their protective effects on photoreceptor cells in light-damaged mouse retinas - Zehai Long; Xiaoye Du; Qiyao Wang; Zhijian Xu; Bo Li; Yong Zhang; Yu Chen; Qi Jia; Yiming Li; Weiliang Zhu (Natural Product Research, 2022)

miR171 modulates induction of somatic embryogenesis in citrus callus - Qiao-Fang Shi; Jian-Mei Long; Zhao-Ping Yin; Nan Jiang; Meng-Qi Feng; Bo Zheng; Wen-Wu Guo; Xiao-Meng Wu (Plant Cell Reports, 2022)

The behavior of REEs indicates the dolomite petrogenesis and a unique dolomitization model of the Middle Permian Qixia formation in Northwest Sichuan Basin, China - Shengyang Xie; Xingzhi Wang; Bo Li; Long Wen; Liang Xu; Yao Du; Lin Xie; Yong Li; Yaping Wang; Yawen Li (Carbonates and Evaporites, 2022)

Landslides triggered by the 1970 Ms 7.7 Tonghai earthquake in Yunnan, China: an inventory, distribution characteristics, and tectonic significance - Yu-long Cui; Jun-hong Hu; Chong Xu; Hai-bo Miao; Jun Zheng (Journal of Mountain Science, 2022)

Episodic Neoproterozoic extension-related magmatism in the Altyn Tagh, NW China: implications for extension and breakup processes of Rodinia supercontinent - Jiang-bo Hao; Chao Wang; Ji-heng Zhang; Liang Liu; Yong-sheng Gai; Hang Li; Zun-pu Yu; Joseph G Meert; Xiao-ping Long; Xiao-kui Sun; Shuai Zhang (International Geology Review, 2022)

Approximate analytical solution for seepage field of drained tunnel in vertically stratified phreatic aquifer - Wei Meng; Chuan He; Fang-yin Wu; Wen-bo Yang; Hao Kou; Zi-han Zhou; De-ping Guo; Hai-long Meng (Journal of Mountain Science, 2022)

General anesthesia bullies the gut: a toxic relationship with dysbiosis and cognitive dysfunction - Lidan Liu; Lihua Shang; Dongxue Jin; Xiuying Wu; Bo Long (Psychopharmacology, 2022)

Laboratory Characterization of Surfactant-Enhanced Air Sparging Effectiveness on VOC-Contaminated Soil with Low Permeability - Fusheng Zha; Haonan Li; Long Xu; Bo Kang; Xianguo Sun (Water, Air, & Soil Pollution, 2022)

Potential Effect of the Intrusion of the Kuroshio Current into the South China Sea on Catches of Japanese Eel (Anguilla Japonica) in the South China Sea and Taiwan Strait - Ching-Hsien Ho; Long-Jing Wu; Zhen Lu; Bo-Yi Lu; Yang-Chi Lan (Journal of Marine Science and Engineering, 2021)
This study examined the effect of the intrusion of the Kuroshio Current (KC) into the South China Sea (SCS) and the Taiwan Strait (TS) (SCS–TS region) on changes in catches of larval A. japonica in the traditional fishing ground waters of Gaoping near southwestern Taiwan in the SCS–TS region. First, the oceanic environment and recruitment trends from 1967 to 2019 were investigated based on secondary data. Then, field surveys were conducted to obtain primary data regarding the intrusion of the KC into the SCS, as well as the changes in the fishing sites and catches of A. japonica in the fall and winter of 2014–2015. Hence, the association between oceanic conditions and the number of A. japonica migrating into the SCS–TS region was explored. From 1967 to 2019, the recruitment proportion in the fishing grounds that formed due to the Kuroshio Branch Current (PKSBC) fluctuated significantly. Overall, positive values were observed for the Oceanic Niño Index for each year with a PKSBC > 50%, corresponding to El Niño conditions. In each year with a PKSBC > 70%, a looping path and a warm–core eddy appeared.

Optimization of the factors affecting droplet deposition in rice fields by rotary unmanned aerial vehicles (UAVs) - Shuang Guo; Jiyu Li; Weixiang Yao; Xiaodan Hu; Xu Wei; Bo Long; Han Wu; Huifen Li (Precision Agriculture, 2021)

Biodiversity-based development and evolution: the emerging research systems in model and non-model organisms - Long Zhao; Feng Gao; Shan Gao; Yujun Liang; Hongan Long; Zhiyi Lv; Ying Su; Naihao Ye; Liusuo Zhang; Chengtian Zhao; Xiaoyu Wang; Weibo Song; et al. (Science China Life Sciences, 2021)

First report of leaf spot on sorghum caused by Pestalotiopsis trachycarpicola in China - Juan Fan; Hong Bo Qiu; Hai Jiang Long; Wei Zhao; Xiao Long Xiang; An Long Hu (Journal of Plant Pathology, 2021)

A catastrophic natural disaster chain of typhoon-rainstorm-landslide-barrier lake-flooding in Zhejiang Province, China - Yu-long Cui; Jun-hong Hu; Chong Xu; Jun Zheng; Jiang-bo Wei (Journal of Mountain Science, 2021)

Failure mechanisms and dynamics of the Shanzao rockslide in Yongjia County, China on 10 August 2019 - Youyin Wu; Ming Zhang; Long Yang; Tao Liu; Taili Zhang; Qiang Sun; Bo Wang; Xinpeng Xie (Landslides, 2021)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Enhanced treatment of shale gas fracturing waste fluid through plant-microbial synergism - Bo Shao; Xu Tan; Ju-Long Li; Mei He; Lei Tian; Wen-Jie Chen; Yan Lin (Environmental Science and Pollution Research, 2021)

Assessment of 12 Essential and Toxic Elements in Whole Blood of Pregnant and Non-pregnant Women Living in Wuhan of China - Lu Gong; Qing Yang; Chang-Wen-Bo Liu; Xu Wang; Hao-Long Zeng (Biological Trace Element Research, 2021)

Experimental study on adsorption promotion and desorption restrain of gas-containing coal in low-temperature environment - Fakai Wang; Xuelong Li; Bo Cui; Jian Hao; Xin Gao; Kun Long; Peng Chen; Sheng Wang (Arabian Journal of Geosciences, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Correction to: Bio-electrospraying is a safe technology for delivering human adipose-derived stem cells - Chuan Ye; Zhixu He; Yunfeng Lin; Yi Zhang; Jin Tang; Bo Sun; Minxian Ma; Jielin Liu; Long Yang; Houxiang Ren; Baoping Zhao (Biotechnology Letters, 2021)

Slip rates and paleoearthquakes along the east segment of the Guanggaishan–Dieshan fault zone, West Qinling Range, NW China - Bo Zhang; Aiguo Wang; Daoyang Yuan; Qinjian Tian; Xiaofeng Liu; Long Zheng; Ming Wu (International Journal of Earth Sciences, 2021)

A rare mutant of OFD1 gene responsible for Joubert syndrome with significant phenotype variation - Yang-wei Zhang; Hai-bo Qu; Ning Long; Xiang-you Leng; Yun-qiang Liu; Yuan Yang (Molecular Genetics and Genomics, 2021)

The effect of aging on VEGF/VEGFR2 signal pathway genes expression in rat liver sinusoidal endothelial cell - Wan-Li Wang; Xing-Long Zheng; Qing-Shan Li; Wen-Yan Liu; Liang-Shuo Hu; Huan-Chen Sha; Kun Guo; Yi Lv; Bo Wang (Molecular and Cellular Biochemistry, 2021)

Distribution characteristics and main influencing factors of selenium in surface soil of natural selenium-rich area: a case study in Langao County, China - Litao Hao; Jiandong Zhang; Shixi Zhang; Sumin Ma; Bo Li; Jie Long; Jingsen Fan; Kunli Luo (Environmental Geochemistry and Health, 2021)

A unique porin meditates iron‐selective transport through cyanobacterial outer membranes - Guo‐Wei Qiu; Hai‐Bo Jiang; Hagar Lis; Zheng‐Ke Li; Bin Deng; Jin‐Long Shang; Chuan‐Yu Sun; Nir Keren; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Cyanobacteria are globally important primary producers and nitrogen fixers with high iron demands. Low ambient dissolved iron concentrations in many aquatic environments mean that these organisms must maintain sufficient and selective transport of iron into the cell. However, the nature of iron transport pathways through the cyanobacterial outer membrane remains obscure. Here we present multiple lines of experimental evidence that collectively support the existence of a novel class of substrate‐selective iron porin, Slr1908, in the outer membrane of the cyanobacterium Synechocystis sp. PCC 6803. Elemental composition analysis and short‐term iron uptake assays with mutants in Slr1908 reveal that this protein is primarily involved in inorganic iron uptake and contributes less to the accumulation of other metals. Homologues of Slr1908 are widely distributed in both freshwater and marine cyanobacteria, most notably in unicellular marine diazotrophs. Complementary experiments with a homologue of Slr1908 in Synechococcus sp. PCC 7002 restored the phenotype of Synechocystis knockdown mutants, showing that this siderophore producing species also possesses a porin with a similar function in Fe transport. The involvement of a substrate‐selective porins in iron uptake may allow cyanobacteria to tightly control iron flux into the cell, particularly in environments where iron concentrations fluctuate.

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Fine-Grained Topography and Modularity of the Macaque Frontal Pole Cortex Revealed by Anatomical Connectivity Profiles - Bin He; Long Cao; Xiaoluan Xia; Baogui Zhang; Dan Zhang; Bo You; Lingzhong Fan; Tianzi Jiang (Neuroscience Bulletin, 2020)
The frontal pole cortex (FPC) plays key roles in various higher-order functions and is highly developed in non-human primates. An essential missing piece of information is the detailed anatomical connections for finer parcellation of the macaque FPC than provided by the previous tracer results. This is important for understanding the functional architecture of the cerebral cortex. Here, combining cross-validation and principal component analysis, we formed a tractography-based parcellation scheme that applied a machine learning algorithm to divide the macaque FPC (2 males and 6 females) into eight subareas using high-resolution diffusion magnetic resonance imaging with the 9.4T Bruker system, and then revealed their subregional connections. Furthermore, we applied improved hierarchical clustering to the obtained parcels to probe the modular structure of the subregions, and found that the dorsolateral FPC, which contains an extension to the medial FPC, was mainly connected to regions of the default-mode network. The ventral FPC was mainly involved in the social-interaction network and the dorsal FPC in the metacognitive network. These results enhance our understanding of the anatomy and circuitry of the macaque brain, and contribute to FPC-related clinical research.

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Physical structure and phytoplankton community off the eastern Hainan coast during summer 2015 - Sumin Liu; Bo Hong; Guifen Wang; Weiqiang Wang; Qiang Xie; Zekai Ni; Liu Yu; Huichang Jiang; Tong Long; Hongzhou Xu (Acta Oceanologica Sinica, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Dynamic Change of Shanks Gene mRNA Expression and DNA Methylation in Epileptic Rat Model and Human Patients - Yujiao Fu; Du Liu; Jialing Guo; Hongyu Long; Wenbiao Xiao; Wei Xiao; Li Feng; Zhaohui Luo; Bo Xiao (Molecular Neurobiology, 2020)

Hearing impairment-associated KARS mutations lead to defects in aminoacylation of both cytoplasmic and mitochondrial tRNALys - Yong Wang; Jing-Bo Zhou; Qi-Yu Zeng; Siqi Wu; Mei-Qin Xue; Pengfei Fang; En-Duo Wang; Xiao-Long Zhou (Science China Life Sciences, 2020)

First record of field dodder (Cuscuta campestris) parasitizing invasive buffalobur (Solanum rostratum) - Wei-Bin Wang; Fan-Fan Gao; Mei-Ni Shao; Ming-Chao Liu; Hong-Feng Zhai; Bo Qu; Yu-Long Feng (Journal of Plant Pathology, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Overload type and optimization of meadow carrying capacity in Maqin County in the Three-River Source Region, China - Jin-jin Sun; Peng-bin Wang; Yong-shang Tong; Yuan-yuan Hao; You-long He; Hai-bo Wang; Xiao-jun Yu (Journal of Mountain Science, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Effect of three Napier grass varieties on phytoextraction of Cd- and Zn-contaminated cultivated soil under mowing and their safe utilization - Wen-Jun Yang; Jiao-Feng Gu; Hang Zhou; Fang Huang; Teng-Yue Yuan; Jing-Yi Zhang; Shi-Long Wang; Zhi-Guang Sun; Hong-Wei Yi; Bo-Han Liao (Environmental Science and Pollution Research, 2020)

Corrigendum: Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Bo Yang; Emmanuel S. Boss; Nils Haëntjens; Matthew C. Long; Michael J. Behrenfeld; Rachel Eveleth; Scott C. Doney (Frontiers in Marine Science, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Bo Yang; Emmanuel S. Boss; Nils Haëntjens; Matthew C. Long; Michael J. Behrenfeld; Rachel Eveleth; Scott C. Doney (Frontiers in Marine Science, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Characteristics of paleogeomorphology and paleokarstification and the impact on natural gas accumulation: a case study of upper assemblage of Majiagou formation in central Sulige gas field, Ordos Basin, China - Liwen Zhu; Zhenliang Wang; Bo Zhang; Li Wei; Qianghan Feng; Xun Lei; Long Chen (Carbonates and Evaporites, 2019)

Evaluating gravity gradient components based on a reweighted inversion method - Ju-Liang Cao; Peng-Bo Qin; Zhen-Long Hou (Applied Geophysics, 2019)

Network and Pathway-Based Analysis of Single-Nucleotide Polymorphism of miRNA in Temporal Lobe Epilepsy - Wenbiao Xiao; Yanhao Wu; Jianjian Wang; Zhaohui Luo; Lili Long; Na Deng; Shangwei Ning; Yi Zeng; Hongyu Long; Bo Xiao (Molecular Neurobiology, 2019)

Assessment of strength and leaching characteristics of heavy metal–contaminated soils solidified/stabilized by cement/fly ash - Fusheng Zha; Chunjie Ji; Long Xu; Bo Kang; Chengbin Yang; Chengfu Chu (Environmental Science and Pollution Research, 2019)

Monitoring of displacement evolution during the pre-failure stage of a rock block using ground-based radar interferometry - Hai-bo Li; Xing-guo Yang; Hai-long Sun; Shun-chao Qi; Jia-wen Zhou (Landslides, 2019)

Analysis of urinary trace element levels in general population of Wuhan in central China - Hao-Long Zeng; Chang-Wen-Bo Liu; Jie Lu; Xu Wang; Liming Cheng (Environmental Science and Pollution Research, 2019)

Numerical simulation of ground motion amplification in Modong area, Lushan - Chao Han; Jiashun Yu; Wei-Zu Liu; Jian-Long Yuan; Xiao-Bo Fu; Xiao-Ping Hou (Applied Geophysics, 2019)

Implementation of quasi-real-time estimation of BDS clock - Wei Ning; Jian-Bo Wang; Long-Jiang Tang (Acta Geophysica, 2019)

Analysis of the Seismic Effect of Slopes with Different Shapes Under Dynamic Loads - Gui-Lin Wang; Liang Zhang; Zhi-Wen Huang; Bo-Long Liu; Pei-Yong Qiu (Geotechnical and Geological Engineering, 2019)

Quantitative Evaluation Methods of Brittle Failure Characteristics of Coal: A Case Study of Hard Coal in China - Bo Ren; Shao-hua Wang; Jun-hua Xue; Kai-long Qiu; Guo-feng Yu; Ying-jie Fan; Shi-qi Zhao; Zhen-yu Du; Dong-sheng Deng; Xian-jie Hao (Geotechnical and Geological Engineering, 2019)

Comparative expression analysis of let-7 microRNAs during ovary development in Megalobrama amblycephala - Tian Lan; Yu-Long Chen; Yasmeen Gul; Bo-Wen Zhao; Ze-Xia Gao (Fish Physiology and Biochemistry, 2019)

Global trends and future prospects of e-waste research: a bibliometric analysis - Ya Gao; Long Ge; Shuzhen Shi; Yue Sun; Ming Liu; Bo Wang; Yi Shang; Jiarui Wu; Jinhui Tian (Environmental Science and Pollution Research, 2019)

Soil erosion of unpaved loess roads subjected to an extreme rainstorm event: a case study of the Jiuyuangou watershed on the Loess Plateau, China - Bo Yang; Wen-long Wang; Ming-ming Guo; Wen-zhao Guo; Wen-xin Wang; Hong-liang Kang; Man Zhao; Zhuo-xin Chen (Journal of Mountain Science, 2019)

Antimicrobial susceptibility and molecular typing of Pasteurella multocida isolated from six provinces in China - Ling-Cong Kong; Zi Wang; Yi-Ming Wang; Wen-Long Dong; Bo-Yan Jia; Duo Gao; Xiu-Yun Jiang; Hong-Xia Ma (Tropical Animal Health and Production, 2019)

Polymorphism analyses of 19 STRs in Labrador Retriever population from China and its heterozygosity comparisons with other retriever breeds - Meng-Lei Wang; Xiao-Ye Jin; Xin Xiong; Jin-Long Yang; Jian-Ping Li; Qi Wang; Bo-Feng Zhu; Ya-Jun Deng (Molecular Biology Reports, 2019)

Bazedoxifene protects cerebral autoregulation after traumatic brain injury and attenuates impairments in blood–brain barrier damage: involvement of anti-inflammatory pathways by blocking MAPK signaling - Yu-Long Lan; Xun Wang; Yu-Jie Zou; Jin-Shan Xing; Jia-Cheng Lou; Shuang Zou; Bin-Bin Ma; Yan Ding; Bo Zhang (Inflammation Research, 2019)

Cyclic loading–unloading creep behavior of composite layered specimens - Bo Hu; Sheng-Qi Yang; Peng Xu; Jian-Long Cheng (Acta Geophysica, 2019)

Detection of lncRNA-mRNA interaction modules by integrating eQTL with weighted gene co-expression network analysis - Xing-Bo Mo; Long-Fei Wu; Xin Lu; Xiao-Wei Zhu; Wei Xia; Lan Wang; Pei He; Peng-Fei Bing; Yong-Hong Zhang; Fei-Yan Deng; Shu-Feng Lei (Functional & Integrative Genomics, 2019)

Molecular surveillance of coxsackievirus A16 reveals the emergence of a new clade in mainland China - Long Chen; Xiang-Jie Yao; Shao-Jian Xu; Hong Yang; Chun-Li Wu; Jing Lu; Wen-Bo Xu; Hai-Long Zhang; Jun Meng; Yong Zhang; Ya-Qing He; Ren-Li Zhang (Archives of Virology, 2019)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

The East Asiatic region of crop plant diversity - Bo Liu; Karl Hammer; Sizhao Liu; Chunlin Long (Genetic Resources and Crop Evolution, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Evaluation of Calcium Oxide of Quicklime and Si–Ca–Mg Fertilizer for Remediation of Cd Uptake in Rice Plants and Cd Mobilization in Two Typical Cd-Polluted Paddy Soils - Xin-Yang Li; Jian Long; Pei-Qin Peng; Qi Chen; Xia Dong; Kai Jiang; Hong-Bo Hou; Bo-Han Liao (International Journal of Environmental Research, 2018)

The phosphatidylinositol synthase gene (GhPIS) contributes to longer, stronger, and finer fibers in cotton - Qin Long; Fang Yue; Ruochen Liu; Shuiqing Song; Xianbi Li; Bo Ding; Xingying Yan; Yan Pei (Molecular Genetics and Genomics, 2018)

Short-Term Exposure to Lambda-Cyhalothrin Negatively Affects the Survival and Memory-Related Characteristics of Worker Bees Apis mellifera - Chun-hua Liao; Xu-jiang He; Zi-long Wang; Andrew B. Barron; Bo Zhang; Zhi-jiang Zeng; Xiao-bo Wu (Archives of Environmental Contamination and Toxicology, 2018)

GbABR1 is associated with Verticillium wilt resistance in cotton - Yujia Liu; Xin Liu; Lu Long; Weina Wang; Quan Sun; Bo Li; Chenxiao Wang; Jieru Cheng; Yuanyuan Zhang; Yuanhui Xie; Lingling Xu; Runkuan Qin; et al. (Biologia, 2018)

Construction and biocompatibility of a thin type I/II collagen composite scaffold - Long Han; Zhong-wen Zhang; Bo-he Wang; Zhen-kun Wen (Cell and Tissue Banking, 2018)

The distribution and functional relevance analysis of runs of homozygosity (ROHs) in Chinese Han female population - Yi-Hua Lu; Bing-Hua Wang; Wei Xia; Xing-Bo Mo; Long-Fei Wu; Xiao-Wei Zhu; Pei He; Fang-Fei Xie; Xin Lu; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Molecular characterization and recombination analysis of porcine reproductive and respiratory syndrome virus emerged in southwestern China during 2012–2016 - Long Zhou; Runmin Kang; Gaosheng Ji; Yiming Tian; Mengyun Ge; Bo Xie; Xin Yang; Hongning Wang (Virus Genes, 2018)

Genome-Wide DNA Methylation Patterns Analysis of Noncoding RNAs in Temporal Lobe Epilepsy Patients - Wenbiao Xiao; Yuze Cao; Hongyu Long; Zhaohui Luo; Shuyu Li; Na Deng; Jianjian Wang; Xiaoyan Lu; Tianfeng Wang; Shangwei Ning; Lihua Wang; Bo Xiao (Molecular Neurobiology, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Impacts of soil properties on phosphorus adsorption and fractions in purple soils - Yi Xiao; Jia-liang Tang; Ming-kuang Wang; Long-bo Zhai; Xi-feng Zhang (Journal of Mountain Science, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

The potential roles of dopamine in malignant glioma - Yu-Long Lan; Xun Wang; Jin-Shan Xing; Jia-Cheng Lou; Xiao-Chi Ma; Bo Zhang (Acta Neurologica Belgica, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Heterogeneity of hydraulic conductivity and Darcian flux in the submerged streambed and adjacent exposed stream bank of the Beiluo River, northwest China - Jinxi Song; Weiwei Jiang; Shaofeng Xu; Guotao Zhang; Liping Wang; Min Wen; Bo Zhang; Yuanyuan Wang; Yongqing Long (Hydrogeology Journal, 2016)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

Downregulation of KDM4A Suppresses the Survival of Glioma Cells by Promoting Autophagy - Bo Wang; Xinxin Fan; Chong Ma; Hui Lei; Qianfa Long; Yuan Chai (Journal of Molecular Neuroscience, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

Simulation of Water Quality under Different Reservoir Regulation Scenarios in the Tidal River - Tao Jiang; Ming Zhong; Ying-jie Cao; Long-jian Zou; Bo Lin; Ai-ping Zhu (Water Resources Management, 2016)

Erratum to: Progressive changes of orexin system in a rat model of 6-hydroxydopamine-induced Parkinson’s disease - Long-Biao Cui; Bo-Wei Li; Xiao-Hang Jin; Lin Zhao; Juan Shi (Neuroscience Bulletin, 2016)

Altitude underlies variation in the mating system, somatic condition, and investment in reproductive traits in male Asian grass frogs (Fejervarya limnocharis) - Long Jin; Sheng Nan Yang; Wen Bo Liao; Stefan Lüpold (Behavioral Ecology and Sociobiology, 2016)

Learning curves of percutaneous endoscopic lumbar discectomy in transforaminal approach at the L4/5 and L5/S1 levels: a comparative study - Xin-bo Wu; Guo-xin Fan; Xin Gu; Tu-gang Shen; Xiao-fei Guan; An-nan Hu; Hai-long Zhang; Shi-sheng He (Journal of Zhejiang University-SCIENCE B, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Impact of Biological Treatment Techniques on Perfluoroalkyl Acids Emissions in Municipal Sewage - Xinxuan Wang; Ruobing Zhang; Hong Zhang; Long He; Jincan Shen; Zhifang Chai; Bo Yang; Yanping Wang (Water, Air, & Soil Pollution, 2016)

Optimizing schemes on dynamic control of reservoir normal elevation in flood season - Xiao-lu Meng; Xiu-juan Liang; Bai-zhong Yan; Wei Li; Long-hao Guo; Bo Feng (Natural Hazards, 2016)

Prediction of drug-induced eosinophilia adverse effect by using SVM and naïve Bayesian approaches - Hui Zhang; Peng Yu; Ming-Li Xiang; Xi-Bo Li; Wei-Bao Kong; Jun-Yi Ma; Jun-Long Wang; Jin-Ping Zhang; Ji Zhang (Medical & Biological Engineering & Computing, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

The Ephrin-A5/EphA4 Interaction Modulates Neurogenesis and Angiogenesis by the p-Akt and p-ERK Pathways in a Mouse Model of TLE - Yi Shu; Bo Xiao; Qian Wu; Tiantian Liu; Yang Du; Haiyun Tang; Si Chen; Li Feng; Lili Long; Yi Li (Molecular Neurobiology, 2016)

Changes in digestive enzyme activities during larval development of Chinese loach Paramisgurnus dabryanus (Dabry de Thiersant, 1872) - Yun-Long Zhang; Qiao-Wan Wu; Wei-Hua Hu; Fan Wang; Zhong-Bo Zhao; Hui He; Wei-Han Shao; Qi-Xue Fan (Fish Physiology and Biochemistry, 2015)

Erratum to: Rapid and environmentally-friendly extraction of carotenoids from Blakeslea trispora - Hong-Bo Wang; Li-Wei Zhang; Jun Luo; Long-Jiang Yu (Biotechnology Letters, 2015)

Rapid and environmentally-friendly extraction of carotenoids from Blakeslea trispora - Hong-Bo Wang; Li-Wei Zhang; Jun Luo; Long-Jiang Yu (Biotechnology Letters, 2015)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Functions for the cAMP/Epac/Rap1 Signaling Pathway in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Seasonality and Age is Positively Related to Brain Size in Andrew’s Toad (Bufo andrewsi) - Ao Jiang; Mao Jun Zhong; Min Xie; Shang Ling Lou; Long Jin; Jehle Robert; Wen Bo Liao (Evolutionary Biology, 2015)

Oceanobacillus damuensis sp. nov. and Oceanobacillus rekensis sp. nov., isolated from saline alkali soil samples - Xiufeng Long; Renyuan Ye; Shuai Zhang; Bo Liu; Yuqin Zhang; Zhigang Zeng; Yongqiang Tian (Antonie van Leeuwenhoek, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Phthalate esters contamination in soils and vegetables of plastic film greenhouses of suburb Nanjing, China and the potential human health risk - Ting Ting Ma; Long Hua Wu; Like Chen; Hai Bo Zhang; Ying Teng; Yong Ming Luo (Environmental Science and Pollution Research, 2015)

Growth Inhibition and Altered Gene Transcript Levels in Earthworms (Eisenia fetida) Exposed to 2,2′,4,4′-Tetrabromodiphenyl Ether - Xiang-bo Xu; Ya-juan Shi; Yong-long Lu; Xiao-qi Zheng; R. J. Ritchie (Archives of Environmental Contamination and Toxicology, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Expression profiles of miRNAs in Gossypium raimondii - Jun Ma; Teng-long Guo; Qing-lian Wang; Kun-bo Wang; Run-run Sun; Bao-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Correlation of an interleukin-4 gene polymorphism with susceptibility to severe enterovirus 71 infection in Chinese children - Fei Li; Xiang-ping Liu; Ji-an Li; Zhen-liang Han; Pei-pei Liu; Yuan-yuan Wang; Long Song; Zong-bo Chen (Archives of Virology, 2015)

Erratum to: Phylogenetic Analyses on the Diversity of Aspergillus fumigatus Sensu Lato Based on Five Orthologous Loci - Fang Li; Bo Wang; Long Wang; Bin Cao (Mycopathologia, 2015)

Effect of zero-valent iron on the start-up performance of anaerobic ammonium oxidation (anammox) process - Long-Fei Ren; Shou-Qing Ni; Cui Liu; Shuang Liang; Bo Zhang; Qiang Kong; Ning Guo (Environmental Science and Pollution Research, 2015)

Bio-electrospraying is a safe technology for delivering human adipose-derived stem cells - Chuan Ye; Zhixu He; Yunfeng Lin; Yi Zhang; Jin Tang; Bo Sun; Minxian Ma; Jielin Liu; Long Yang; Houxiang Ren; Baoping Zhao (Biotechnology Letters, 2015)

Cognitive disorders in HIV-infected and AIDS patients in Guangxi, China - Tingting Zhao; Bo Wei; Jianxiong Long; Xianyan Tang; Mengxiao Zhou; Chao Dang (Journal of NeuroVirology, 2015)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Cloning and respond of a cold shock domain protein (CnCSDP) gene to cold stress in noble scallop Chlamys nobilis (Bivalve: Pectinidae) - Ya-Jun Wang; Huai-Ping Zheng; Bo Zhang; He-Lu Liu; Hua-Juan Deng; Long-Hui Deng (Molecular Biology Reports, 2014)

Mechanical Model for Predicting Closure Behavior of Rock Joints Under Normal Stress - Zhi-Cheng Tang; Quan-Sheng Liu; Cai-Chu Xia; Ying-Long Song; Ji-Hui Huang; Chun-Bo Wang (Rock Mechanics and Rock Engineering, 2014)

Identification and characterization of a novel phage display-derived peptide with affinity for human brain metastatic breast cancer - Bo Fu; Ying Zhang; Wei Long; Aifeng Zhang; Yafen Zhang; Yanli An; Fengqin Miao; Fang Nie; Mingli Li; Youji He; Jianqiong Zhang; Gaojun Teng (Biotechnology Letters, 2014)

Phylogenetic Analyses on the Diversity of Aspergillus fumigatus Sensu Lato Based on Five Orthologous Loci - Fang Li; Bo Wang; Long Wang; Bin Cao (Mycopathologia, 2014)

Variation in β-amylase activity and thermostability in Tibetan annual wild and cultivated barley genotypes - Hai-tao Zhang; Tian-long Chen; Bing-lin Zhang; De-zhi Wu; Ye-chang Huang; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Assessment of gene flow from glyphosate-resistant transgenic soybean to conventional soybean in China - Wen-Kun Huang; Huan Peng; Gao-Feng Wang; Jiang-Kuan Cui; Lin-Feng Zhu; Hai-Bo Long; De-Liang Peng (Acta Physiologiae Plantarum, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Adipose-derived stem cells transfected with pEGFP-OSX enhance bone formation during distraction osteogenesis - Qing-guo Lai; Shao-long Sun; Xiao-hong Zhou; Chen-ping Zhang; Kui-feng Yuan; Zhong-jun Yang; Sheng-lei Luo; Xiao-peng Tang; Jiang-bo Ci (Journal of Zhejiang University-SCIENCE B, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Fluid inclusion and isotope geochemistry of the Yangla copper deposit, Yunnan, China - Xi-An Yang; Jia-Jun Liu; Long-Bo Yang; Si-Yu Han; Xiao-Ming Sun; Huan Wang (Mineralogy and Petrology, 2014)

A monocarbonyl analogue of curcumin, 1,5-bis(3-hydroxyphenyl)-1,4-pentadiene-3-one (Ca 37), exhibits potent growth suppressive activity and enhances the inhibitory effect of curcumin on human prostate cancer cells - Cheng Luo; Yan Li; Bo Zhou; Liang Yang; Hua Li; Zhihui Feng; Yuan Li; Jiangang Long; Jiankang Liu (Apoptosis, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Effects of four antitussives on airway neurogenic inflammation in a guinea pig model of chronic cough induced by cigarette smoke exposure - Yu-long Luo; Pei-bo Li; Chen-chen Zhang; Yan-fang Zheng; Sheng Wang; Yi-chu Nie; Ke-jian Zhang; Wei-wei Su (Inflammation Research, 2013)

BRSK2 is a valosin-containing protein (VCP)-interacting protein that affects VCP functioning in endoplasmic reticulum-associated degradation - Yingli Wang; Bo Wan; Jun Zhou; Ruwei Li; Long Yu (Biotechnology Letters, 2013)

A study of a rare chromosomal disorder: mosaic 46,XX,del(18)(p11.2)/46,XX,i(18q) - DAN PENG; PAN-PAN LONG; BO WEN; RONG-HUI YU (Journal of Genetics, 2013)

Investigation of individual heterozygosity correlated to growth traits in Tongshan Black-boned goat - Yan Guo Han; Gui Qiong Liu; Xun Ping Jiang; Guo Ming Liang; Chun Bo He; Dang Wei Wang; Yan Wu; Xing Long Xiang; Jie Hu; Yu Qin Peng (Molecular Biology Reports, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

OsSNDP1, a Sec14-nodulin domain-containing protein, plays a critical role in root hair elongation in rice - Jin Huang; Chul Min Kim; Yuan-hu Xuan; Soon Ju Park; Hai Long Piao; Byoung Il Je; Jingmiao Liu; Tae Ho Kim; Bo-Kyeong Kim; Chang-Deok Han (Plant Molecular Biology, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Analysis of selected singleton transposable elements (SSTEs) and their application for the development of land PATE markers in Magnaporthe oryzae - Hong-yan Zhang; Dong-yang He; Teerapong Kasetsomboon; Heng Zhou; Ping Li; Xiang-long Li; Chatchawan Jantasuriyarat; Bo Zhou (Journal of General Plant Pathology, 2013)

Genomewide analysis indicates that queen larvae have lower methylation levels in the honey bee (Apis mellifera) - Yuan Yuan Shi; Wei Yu Yan; Zachary Y. Huang; Zi Long Wang; Xiao Bo Wu; Zhi Jiang Zeng (The Science of Nature, 2013)

Diversity of culturable root-associated/endophytic bacteria and their chitinolytic and aflatoxin inhibition activity of peanut plant in China - Kai Wang; Pei-sheng Yan; Qing-long Ding; Qin-xi Wu; Zhong-bo Wang; Jie Peng (World Journal of Microbiology and Biotechnology, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Novel and ancient HMW glutenin genes from Aegilops tauschii and their phylogenetic positions - Wen-Jie Chen; Xing Fan; Bo Zhang; Bao-Long Liu; Ze-Hong Yan; Lian-Quan Zhang; Zhong-Wei Yuan; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Possible Correlation between Selenoprotein W and Myogenic Regulatory Factors in Chicken Embryonic Myoblasts - Qiong Wu; Hai-Dong Yao; Zi-Wei Zhang; Bo Zhang; Fan-Yu Meng; Shi-Wen Xu; Xiao-Long Wang (Biological Trace Element Research, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Saturated fatty acid induction of endoplasmic reticulum stress and apoptosis in human liver cells via the PERK/ATF4/CHOP signaling pathway - Jie Cao; Dong-Ling Dai; Long Yao; Hui-Hong Yu; Bo Ning; Qin Zhang; Juan Chen; Wen-Hui Cheng; Wei Shen; Zhao-Xia Yang (Molecular and Cellular Biochemistry, 2012)

Dietary selenium regulation of transcript abundance of selenoprotein N and selenoprotein W in chicken muscle tissues - Jiu-li Zhang; Jin-Long Li; Xiao-dan Huang; Sun Bo; Wang Rihua; Shu Li; Shi-wen Xu (BioMetals, 2012)

Literature and patent analysis of the cloning and identification of human functional genes in China - Yan Xia; LiSha Tang; Lei Yao; Bo Wan; XianMei Yang; Long Yu (Science China Life Sciences, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

The Potential Influence of Seasonal Climate Variables on the Net Primary Production of Forests in Eastern China - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Jin Long Zhang (Environmental Management, 2011)

Historical and botanical evidence of distribution, cultivation and utilization of Linum usitatissimum L. (flax) in China - Fei-Hu Liu; Xia Chen; Bo Long; Rui-Yan Shuai; Chun-Lin Long (Vegetation History and Archaeobotany, 2011)

Association study of single nucleotide polymorphisms in pre-miRNA and rheumatoid arthritis in a Han Chinese population - Bin Yang; Jun Long Zhang; Yun Ying Shi; Dong Dong Li; Jie Chen; Zhuo Chun Huang; Bei Cai; Xing Bo Song; Li Xin Li; Bin Wu Ying; Lan Lan Wang (Molecular Biology Reports, 2011)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

Fluid Dynamics Analysis of a Novel Micropatterned Cell Bioreactor - Yuhong Cui; Bo Huo; Shujin Sun; Fan Yang; Yuxin Gao; Jun Pan; Mian Long (Annals of Biomedical Engineering, 2011)

Progressive changes of orexin system in a rat model of 6-hydroxydopamineinduced Parkinson’s disease - Cui Long-Biao; Li Bo-Wei; Jin Xiao-Hang; Zhao Lin; Shi Juan (Neuroscience Bulletin, 2010)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

p53 Promotes proteasome-dependent degradation of oncogenic protein HBx by transcription of MDM2 - Lingling Xian; Jing Zhao; Jia Wang; Zhou Fang; Bo Peng; Wenzhang Wang; Xiaona Ji; Long Yu (Molecular Biology Reports, 2010)

AMP-activated protein kinase supports the NGF-induced viability of human HeLa cells to glucose starvation - Luo Ting; Wan Bo; Ruwei Li; Xinya Chen; Yingli Wang; Zhou Jun; Long Yu (Molecular Biology Reports, 2010)

In vitro propagation of four threatened Paphiopedilum species (Orchidaceae) - Bo Long; Alex X. Niemiera; Zhi-ying Cheng; Chun-lin Long (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Identification and characterization of human LYPD6, a new member of the Ly-6 superfamily - Yifeng Zhang; Qingyu Lang; Jie Li; Fang Xie; Bo Wan; Long Yu (Molecular Biology Reports, 2010)

3-Hydroxyflavone inhibits endogenous Aurora B and induces growth inhibition of cancer cell line - Qingyu Lang; Haoxing Zhang; Jie Li; Fang Xie; Yifeng Zhang; Bo Wan; Long Yu (Molecular Biology Reports, 2010)

How tidal regime and treatment timing influence the clipping frequency for controlling invasive Spartina alterniflora: implications for reducing management costs - Long Tang; Yang Gao; Chenghuan Wang; Jinqing Wang; Bo Li; Jiakuan Chen; Bin Zhao (Biological Invasions, 2010)

Effects of Selenium on the Antioxidant Enzymes Response of Neocaridina heteropoda Exposed to Ambient Nitrite - Hong-wei Wang; Hai-ming Xu; Guo-hua Xiao; Chun-long Zhao; Zi-hui Wang; Duan-bo Cai; Hong-quan Li; Jian-hua Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)

In vitro induction of inflorescence in Dioscorea zingiberensis - Xiao-Long Huang; Bo Yang; Chun-Gen Hu; Jia-Ling Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Novel microRNAs uncovered by deep sequencing of small RNA transcriptomes in bread wheat (Triticum aestivum L.) and Brachypodium distachyon (L.) Beauv - Bo Wei; Tao Cai; Rongzhi Zhang; Aili Li; Naxin Huo; Shan Li; Yong Q. Gu; John Vogel; Jizeng Jia; Yijun Qi; Long Mao (Functional & Integrative Genomics, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Surface-bound selectin–ligand binding is regulated by carrier diffusion - Ganyun Sun; Yan Zhang; Bo Huo; Mian Long (European Biophysics Journal, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Toxic Effects of Copper on Antioxidative and Metabolic Enzymes of the Marine Gastropod, Onchidium struma - Xiao-bo Li; Xue-li Hou; Qian Mao; Yun-long Zhao; Yong-xu Cheng; Qun Wang (Archives of Environmental Contamination and Toxicology, 2009)

Cloning and characterization of a human LYPD7, a new member of the Ly-6 superfamily - Jun Ni; Qingyu Lang; Meirong Bai; Chaomin Zhong; Xinya Chen; Bo Wan; Long Yu (Molecular Biology Reports, 2009)

Identification of a novel human lactate dehydrogenase gene LDHAL6A, which activates transcriptional activities of AP1(PMA) - Xinya Chen; Xiuting Gu; Yuxi Shan; Wenwen Tang; Jian Yuan; Zhaomin Zhong; Yingli Wang; Weixue Huang; Bo Wan; Long Yu (Molecular Biology Reports, 2009)

ACL reconstruction with BPTB autograft and irradiated fresh frozen allograft - Kang Sun; Shao-qi Tian; Ji-hua Zhang; Chang-suo Xia; Cai-long Zhang; Teng-bo Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Aqueous two-phase extraction of 2,3-butanediol from fermentation broths by isopropanol/ammonium sulfate system - Li-Hui Sun; Bo Jiang; Zhi-Long Xiu (Biotechnology Letters, 2009)

Cloning and characterization of a human GDPD domain-containing protein GDPD5 - Qingyu Lang; Haoxing Zhang; Jie Li; Hongkun Yin; Yifeng Zhang; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2008)

Identification of TCP10L as primate-specific gene derived via segmental duplication and homodimerization of TCP10L through the leucine zipper motif - Zhaomin Zhong; Jianping Qiu; Xinya Chen; Bo Wan; Jun Ni; Yun Yang; Meirong Bai; Haoxing Zhang; Long Yu (Molecular Biology Reports, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Laser desorption/ionization mass spectrometric study of secondary organic aerosol formed from the photooxidation of aromatics - Mingqiang Huang; Weijun Zhang; Liqing Hao; Zhenya Wang; Wenwu Zhao; Xuejun Gu; Xiaoyong Guo; Xianyun Liu; Bo Long; Li Fang (Journal of Atmospheric Chemistry, 2007)

Cloning and characterization of the human gene RAP2C, a novel member of Ras family, which activates transcriptional activities of SRE - Zekun Guo; Jian Yuan; Wenwen Tang; Xinya Chen; Xiuting Gu; Kuntian Luo; Yingli Wang; Bo Wan; Long Yu (Molecular Biology Reports, 2007)

Cloning and characterization of the human gene DERP6, which activates transcriptional activities of p53 - Jian Yuan; Wenwen Tang; Kuntian Luo; Xinya Chen; Xiuting Gu; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Cloning and Characterization of a Novel, Human Cellular Retinaldehyde-binding Protein CRALBP-like (CRALBPL) Gene - Ya-Hui Kong; Guang-Ming Ye; Kai Qu; Wen-Qi Pan; Xiang-Hua Liu; Bo Wan; Jin-Hu Guo; Long Yu (Biotechnology Letters, 2006)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Identification and Characterization of the Human SCAN Domain Zinc-Finger Gene ZNF449 - Kuntian Luo; Jie Li; Yanhui Cui; Meng Xu; Jian Yuan; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Identification and Characterization of RHEBL1, a Novel Member of Ras Family, which Activates Transcriptional Activities of NF-Kappa B - Jian Yuan; Yuxi Shan; Xinya Chen; Wenwen Tang; Kuntian Luo; Jun Ni; Bo Wan; Long Yu (Molecular Biology Reports, 2005)

Establishment of a xylose metabolic pathway in an industrial strain of Saccharomyces cerevisiae - Ying Wang; Wen-Long Shi; Xiang-Yong Liu; Yu Shen; Xiao-Ming Bao; Feng-Wu Bai; Yin-Bo Qu (Biotechnology Letters, 2004)

GADD45γ, down-regulated in 65% Hepatocellular Carcinoma (HCC) from 23 Chinese patients, inhibits cell growth and induces cell cycle G2/M arrest for Hepatoma Hep-G2 cell lines - Luhong Sun; Ruomu Gong; Bo Wan; Xinghua Huang; Chaoqun Wu; Xirang Zhang; Shouyuan Zhao; Long Yu (Molecular Biology Reports, 2003)

Cloning of human myeloid-associated differentiation marker (MYADM) gene whose expression was up-regulated in NB4 cells induced by all-trans retinoic acid - Wanchang Cui; Long Yu; Hua He; Yaya Chu; Jie Gao; Bo Wan; Lisha Tang; Shouyuan Zhao (Molecular Biology Reports, 2001)

Identification of human, mouse and rat PPP1R14A, protein phosphatase-1 inhibitor subunit 14A, & mapping human PPP1R14A to chromosome 19q13.13-q13.2 - Zhiyi Li; Long Yu; Yazhou Zhang; Jie Gao; Pingzhao Zhang; Bo Wan; Chiyuan Chen; Shouyuan Zhao (Molecular Biology Reports, 2001)